Host-pathogen interactions during early stages of bovine mastitis: divergent macrophage responses to distinct bovine-associated Staphylococci species and strains - Sarah Antonieta de Oliveira Veríssimo; Ygor Fagundes Ruas; Filipe Aguera Pinheiro; Luiza Campos Reis; Bernardina Amorim Uscata; Hiro Goto; Soraia Araújo Diniz; Adriana Cortez; Sarne De Vliegher; Marcos Bryan Heinemann; Eduardo Milton Ramos-Sanchez; Fernando Nogueira de Souza; et al. (Brazilian Journal of Microbiology, 2026)
Background Bovine mastitis is the most economically significantdisease in dairy farming, with Staphylococcus aureus and Staphylococcus chromogenes asprominent agents, the former posing a major threat. As principal immune sentinels in themammary gland, macrophages orchestrate early pathogen recognition and immune activation,critically influencing the trajectory and outcome of infection. Thus, this study aimed tocharacterize the early macrophage responses to distinct bovine-associated S. aureus and S.chromogenes strains. Methods Here, RAW 264.7 cells were challenged with four differentstrains: S. aureus [isolated from nose (SN), and intramammary infection (IMI)] and S.chromogenes [IMI, and teat apex (TA)] were evaluated after 90- and 180-min. Nitric oxide (NO)production was analyzed in the supernatants, and mRNA levels of IL-1β, IL-18, NLRP3, NOS2,Arg1, Bax, and Bcl2 were assessed in the cells. Results Macrophages challenged with S. aureusIMI strains showed elevated Nos2 expression but negligible NO production, indicating a potentialimmune evasion mechanism. The commensal S. aureus SN strain uniquely maintained arginaseexpression, suggesting M2-like polarization that may promote immune tolerance and bacterialcolonization. Both S. aureus strains significantly upregulated the anti-apoptotic Bcl2 gene, atranscriptional response that may be associated with host cell survival, which may facilitatebacterial intracellular persistence. In contrast, S. chromogenes strains induced strong NOS2expression, robust NLRP3 inflammasome activation, and increased IL-1β production, indicatingM1 polarization and a pro-inflammatory response. The pro-apoptotic Bax gene showed an earlydecrease followed by a later increase exclusively in S. aureus-infected macrophages, indicating atime-dependent transcriptional modulation of apoptosis-related genes. Conclusions Thesegenotype-dependent macrophage responses reveal complex immune modulation shaping mastitis pathogenesis. However, our findings are based solely on transcriptional data on the murine cells and require further validation.

Controls on heterogeneity and mechanical behavior in immature organic-rich carbonates: Insights from an inter-well transect, Al-Lajjun, central Jordan - Samer Aljurf; Israa S. Abu-Mahfouz; Ammar El-Husseiny; Maria Ardila-Sanchez (Journal of African Earth Sciences, 2026)

Evolution of Maastrichtian paleoproductivity along the southern Tethys margin (Jordan): From upwelling to runoff - Maria Ardila-Sanchez; Jihede Haj Messaoud; Amir Kalifi; Khalil Ibrahim; Muhammad Usman; Israa S. Abu-Mahfouz; Samer Aljurf; Volker Vahrenkamp; John H. Powell; Frans van Buchem (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Hydrochar post-treatment and biochar impose differential selective pressures shaping rhizosphere microbiomes and plant performance - Lydia Martinez-Sanchez; Isaac Maestro-Gaitán; Angeles de la Rubia; Angel F. Mohedano; Montserrat Tobajas; Maria Reguera (Applied Soil Ecology, 2026)

Spatial models cannot compensate for sampling designs unstructured relative to isotopic variation: implications for baseline isoscape development in the Mediterranean Sea - Sarah Magozzi; Clive N. Trueman; Matthew R.D. Cobain; Kirsteen M. MacKenzie; Katie St. John Glew; José A. Canseco; Eric Díaz-Delgado; Emanuela Fanelli; Paola Rumolo; Joan E. Cartes; Boris Espinasse; Davide Agnetta; et al. (Progress in Oceanography, 2026)

Sustainable next-generation prebiotics for brain health: microbiota–gut–brain axis in neurodegenerative and demyelinating diseases - Luna Barrera-Chamorro; Teresa Gonzalez-de la Rosa; Joaquin Arzalluz-Luque; Maria Torrecillas-Lopez; Elvira Marquez-Paradas; Carmen M. Claro-Cala; Maria D. Navarro-Hortal; Sara Eichau; Maria I. Garcia-Sanchez; Sergio Montserrat-de la Paz (Critical Reviews in Food Science and Nutrition, 2026)

Sex-specific associations between long-term exposure to ambient air pollution and the cardiac conduction system - a longitudinal analysis of the KORA cohort - Yujiao Li; Siqi Zhang; David Diaz-Sanchez; Kathrin Wolf; Ina-Maria Rückert-Eheberg; Stefan Kääb; Georg Schmidt; Alexander Strom; Annette Peters; Alexandra Schneider; Susanne Breitner-Busch (International Journal of Hygiene and Environmental Health, 2026)

Correction: The impact of earthquake-induced debris on the near-field tsunami pedestrian mobility and safety: Tumaco Island case of study - Maria Paula Ávila-Guzmán; Sergio Herrera; Juan Lizarazo-Marriaga; Miguel Rivas; Jorge Sierra; Cristian Arias; Guillermo Ávila; Gabriel Bernal; Juan Sebastián Paéz; Juan Sebastián Florez; Milton Puentes; Ronald Sanchez; et al. (Natural Hazards, 2026)

Projections of suitable habitat loss and its implications in conservation for endemic non-pseudanthial Euphorbioideae (Euphorbiaceae) species in Northeastern Brazil under climate change scenarios - Tiago Oliveira; Yeison Jaroc Lombo-Sanchez; Karen Yuliana Suarez-Contento; Alícia Marques Torres; Jone Clebson Ribeiro Mendes; Vitória Raquel da Silva Lima; Sarah Maria Athiê-Souza (Biodiversity and Conservation, 2026)
Climate change has intensified negative impacts on biodiversity through changes in precipitation patterns and rising global average temperatures. Semi-arid regions, such as parts of Northeastern Brazil, are particularly susceptible to these changes, with projections indicating that they will become hotter and drier, reducing the climatic suitability of several plant species. In this context, endemic and restricted-range species may be highly vulnerable. In this study, we used distribution modeling to estimate potential changes in the geographic distribution and conservation of 12 endemic Euphorbiaceae species from Northeastern Brazil. Species occurrence records were obtained from online biodiversity databases, and the ecological niche models were generated using bioclimatic variables obtained from WorldClim. We applied the MaxEnt algorithm and projected the models using three General Circulation Models (GCMs) under two future climate scenarios: an optimistic scenario (SSP126) and a pessimistic scenario (SSP585), for the period 2080–2100. We found that climate change will have different impacts on the suitable habitat areas for the analyzed taxa. Future projections indicate that in the optimistic scenario, Sebastiania macrocarpa could expand its suitable range by approximately 45%, while Algernonia bahiensis and Microstachys heterodoxa could expand by approximately 39% and 33%, respectively. In contrast, most species are projected to experience severe reductions in climatically suitable areas, especially Stilingia trapezoidea , Microstachys uleana , and Sebastiania jacobinensis , all with losses exceeding 90%. In the pessimistic scenario, habitat contraction becomes even more pronounced, with Stillingia trapezoidea , Microstachys uleana , Ophthalmoblapton pedunculare , and Sebastiania jacobinensis showing losses close to 100%. However, Sebastiania macrocarpa and Algernonia bahiensis maintain potential range expansions even under the most severe scenario. Mabea fistulifera subsp. bahiensis exhibited complete loss of suitable habitat in both future climate scenarios. We also documented a reduction in species richness in all future climate scenarios analyzed. Furthermore, in both climate scenarios, a general trend toward increasing extinction risk is observed for most species. Thus, this study clearly demonstrates that most endemic species in the family are highly vulnerable to various future climate change scenarios and that conservation measures such as the creation of protected areas within the species’ climatically suitable concentrations should be established.

Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

Postnatal particulate matter exposure alters developmental milestones and brain gene expression in apoE transgenic mice in a sex- and genotype-dependent manner - Rocío Rodulfo-Cárdenas; Judit Biosca-Brull; Séfora Barberà-Parada; Raquel Gabaldón-Díaz; Diego Ruiz-Sobremazas; Jordi Blanco; Maria Cabré; José L. Domingo; Caridad López-Granero; Fernando Sanchez-Santed; Maria Teresa Colomina (NeuroToxicology, 2026)

Built by Iron, changed by heat: Mineral bioaccessibility in iron-fortified and processed Hermetia illucens larvae - Tomer First; Jolien de Boer; Miguel Gomez-Sanchez; Carlos López-Portugués; Jorg Bettmer; Maria Montes-Bayón; Dennis G.A.B. Oonincx; Vincenzo Fogliano; Maryia Mishyna (Food Chemistry, 2026)

The impact of earthquake-induced debris on the near-field tsunami pedestrian mobility and safety: Tumaco Island case of study - Maria Paula Ávila-Guzmán; Sergio Herrera; Juan Lizarazo-Marriaga; Miguel Rivas; Jorge Sierra; Cristian Arias; Guillermo Ávila; Gabriel Bernal; Juan Sebastián Paéz; Juan Sebastián Florez; Milton Puentes; Ronald Sanchez; et al. (Natural Hazards, 2026)
Near-field tsunami evacuation planning depends on urban mobility, which can be severely impacted by earthquake-induced debris obstructing evacuation routes. However, most models overlook this factor, underestimating evacuation times. This study presents a comprehensive GIS-based methodology that integrates seismic damage and debris accumulation into pedestrian evacuation modelling. The methodology proposed was applied to Tumaco on the Southern Pacific coast of Colombia, a highly vulnerable city prone to earthquakes and tsunamis. The model incorporates strong motion simulation, local soil response, seismic vulnerability assessment, and tsunami inundation modelling to quantify the impact of debris on pedestrian evacuation. Results show that earthquake-generated debris increases evacuation times, particularly in the first 30 min. By the estimated tsunami arrival (22 min post-earthquake), the number of evacuees reaching safe zones is reduced by 2.6%, representing 766 individuals at risk. The most affected areas are those with narrow streets and high concentrations of vulnerable structures. This study highlights the need to integrate seismic damage into tsunami evacuation planning to enhance disaster preparedness. The proposed methodology provides a more realistic approach to evacuation modeling, offering valuable insights for urban planning and risk mitigation in tsunami-prone regions.

A machine learning framework for California vineyard water status monitoring using sUAS Imagery and short-term meteorological data - Rui Gao; Maria Mar Alsina; Alfonso F. Torres-Rua; Lawrence Hipps; William P. Kustas; Martha Anderson; Héctor Nieto; Andrew J. McElrone; Kyle Knipper; Nicolas Bambach Ortiz; Sebastian J. Castro; John H. Prueger; et al. (Irrigation Science, 2026)
Efficient irrigation management is essential for sustainable crop production under increasing temperatures and tightening water supplies. In vineyards, water status significantly influences vine growth, yield, and fruit quality, and deficit irrigation is often used to impose controlled stress while avoiding damaging levels of water limitation. This creates a practical need for routine, field-scale monitoring of vine water status. In this study, we developed an operational machine-learning framework to estimate grapevine leaf water potential (Ψ leaf ) by integrating daytime sUAS thermal imagery with short-term local meteorological information. When all candidate predictors were included, the trained eXtreme Gradient Boosting (XGB) model achieved R 2 = 0.71, RMSE = 0.14 MPa , and bias = − 0.06 MPa on the independent test dataset. A simplified XGB model using a compact predictor set–maximum air temperature in the 24 h prior to flight, air temperature at flight time, their difference, and canopy temperature – achieved R 2 = 0.63, RMSE = 0.16 MPa , and bias = − 0.06 MPa , with performance not significantly different from the full model at α = 0.05. This reduced-feature formulation supports vineyard-scale Ψ leaf estimation and mapping while maintaining strong predictive skill and low computational burden. Our research highlights the potential for broader applicability, particularly for monitoring rapidly developing hot and dry conditions and supporting adaptive water resource management.

Molecular detection of coronavirus in wild birds from Lima, Peru - Lisseth M. Leiva-Herrera; Carol Sanchez-Chicana; Juan Jimenez-Chunga; Walter Silva; Javier Jara; Maria T. Lopez-Urbina; Armando E. Gonzalez; Nelly G. Cribillero; Luis A. Gomez-Puerta (Veterinary Research Communications, 2026)

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Enhanced acidogenic fermentation of waste sludge via hydrothermal carbonization pretreatment: Process optimization, performance limitations, and carbon pathways - Marco Pesenti; Maria Jose Hernandez Sanchez; Alisar Kiwan; Daniele Pirini; Matteo Grana; Cristian Torri; Elena Ficara; Andrea Turolla (Journal of Environmental Chemical Engineering, 2026)

Correction to: The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2026)

Role of Like Heterochromatin Protein1 (LHP1) in the root apical meristem and stem cell niche maintenance in Arabidopsis - Gabriela Guzmán-Favila; M. Teresa Alejo-Vinogradova; Diego Ornelas-Ayala; José Olvera-Herrera; Rosario Vega-León; Bénédicte Desvoyes; Adriana Garay-Arroyo; Elena R. Alvarez-Buylla; Crisanto Gutierrez; Maria de la Paz Sanchez (Plant Science, 2026)

Mechanistic insights into antibody recognition of tetrodotoxin analogues: Implications for neurotoxicological assessment - Jaume Reverté; Mounira Alkassar; Maria Rambla-Alegre; Andres Sanchez-Henao; Manolis Mandalakis; Panagiota Peristeraki; Francesc X. Sureda; Jorge Diogène; Mònica Campàs (Chemico-Biological Interactions, 2026)

First step to distinguish between domestic and wild pig faecal biomarkers in archaeological sediments - Ane Gorostizu-Orkaiztegi; Alicia Sanchez-Ortega; M. Carmen Sampedro; Vincenza Forgia; Josep Maria Vergès; Asier Vallejo; Ramón J. Barrio (Archaeological and Anthropological Sciences, 2026)
The study of animal domestication and its development is a major challenge in archaeological science, as it integrates knowledge from multiple disciplines. In this sense, distinguishing between wild and domestic pig in archaeological sediments is an important goal in archaeology as it helps to trace the development of domestication in this species. In this manuscript, we report the identification of specific molecular features differentiating wild and domestic pigs using untargeted analysis by high resolution mass spectrometry. Reference samples of modern wild and domestic pigs were collected from various locations to identify characteristic features of each group and to assess their persistence in archaeological sediments samples previously classified as suid using traditional proxies. Distinct resistant to degradation tentative biomarkers for both wild pig and domestic pigs were identified, enabling the classification of archaeological sedimentary remains into these two categories. This work represents the first approach to identifying domestic and wild pig specific, resistant to degradation biomarkers related to animal domestication.

Differential macrophage immune checkpoint expression triggered by bovine-associated staphylococci - Sarah Antonieta de Oliveira Veríssimo; Filipe Aguera Pinheiro; Ygor Fagundes Ruas; Kamila Reis Santos; Eduardo Milton Ramos-Sanchez; Hiro Goto; Soraia Araújo Diniz; Sarne De Vliegher; Marcos Bryan Heinemann; Luiza Campos Reis; Alice Maria Melville Paiva Della Libera; Fernando Nogueira Souza; et al. (Veterinary Immunology and Immunopathology, 2025)

Polystyrene nanoplastic co-exposed to BPA and BPS induces cytotoxicity, genotoxicity, and alters ROS production in HepG2 cells - Cecilia Cristina de Souza Rocha; Caroline Andolfato Sanchez; Marília Cristina Oliveira Souza; Estéfani Maria Treviso; Gabriel Henrique Savietto; Paula Pícoli Devóz; Lucas Victor Pereira de Freitas; Lusânia Maria Greggi Antunes; Jonas Augusto Rizzato Paschoal; Fernando Barbosa Junior (Toxicology in Vitro, 2025)

Identification of Gambierdiscus species from La Réunion and evaluation of toxicity and toxin profile - Lourdes Barreiro-Crespo; Andres Sanchez-Henao; Sandra Gimeno-Monforte; Jaume Reverté; Mònica Campàs; María García-Altares; Alina Tunin-Ley; Fanny Maillot; Cintia Flores; Nicolas Chomérat; Gwenaël Bilien; Takeshi Tsumuraya; et al. (Harmful Algae, 2025)

Interaction between exercise and flaxseed oil intake on hippocampal function of obese mice: the case of GPR120 - Leandro Kansuke Oharomari; Camila Venturini Ayres Cunha; Julia Boro de Lima; Letícia Maria de Paula; Thaiane da Silva Rios; Talitha Silva Meneguelli; Adelino Sanchez Ramos da Silva; José Rodrigo Pauli; Eduardo Ropelle; Dennys Esper Cintra (Food Research International, 2025)

Long-term impact of oral gestational PM10 exposure on morris water maze performance and hippocampal gene expression - Ruiz-Sobremazas Diego; Coca Mario; Morales-Navas Miguel; Nerea Rios Nieto; Rodulfo-Cárdenas Rocío; Colomina Maria Teresa; López-Granero Caridad; Sanchez-Santed Fernando; Perez-Fernandez Cristian (Environmental Toxicology and Pharmacology, 2025)

Effect of controlled human Plasmodium falciparum infection on B cell subsets in individuals with different levels of malaria immunity - Pilar Requena; Gloria Patricia Gómez-Pérez; Matthew B. B. McCall; Diana Barrios; Ruth Aguilar; Julia Fernández-Morata; Marta Vidal; Joseph J. Campo; Carla Sanchez; Maria Yazdabankhsh; B. Kim Lee Sim; Stephen L. Hoffman; et al. (Medical Microbiology and Immunology, 2025)
Continuous exposure to Plasmodium falciparum (Pf) has been associated with alterations in B cells. We investigated the effect of controlled human malaria infection (CHMI) on B cell phenotypes in individuals with different Pf immunity status: malaria-naïve, immunized with PfSPZ-CVac and semi-immune (lifelong-exposed) volunteers. Compared to naïve, semi-immune but not vaccinated individuals, had increased baseline frequencies of immature B cells (CD19 + CD10 + ), active naive (IgD + CD27 − CD21 − ) B cells, active atypical (IgD − CD27 − CD21 − ) memory B cells (MBCs), active classical (IgD − CD27 + CD21 − ) MBCs and CD1c + -B cells but lower frequencies of some IgG + -B cells. The frequencies of CD1c + active atypical MBCs correlated positively with anti-Pf antibodies and negatively with circulating eotaxin levels, while the opposite was observed for IgG + resting atypical MBCs. During early blood-stage infection (day 11 after CHMI), there was an expansion of resting classical (IgD − CD27 + CD21 + ) MBCs in all three groups. Vaccination, compared to placebo, altered the effect of CHMI on B cells, showing a positive association with resting classical MBCs (β = 0.190, 95% CI 0.011–0.368) and active naïve-PD1 + (β = 0.637, 95% CI 0.058 to 1.217) frequencies, and a negative one with CD1c + resting atypical MBCs (β = − 0.328, 95% CI − 0.621 to − 0.032). In addition, the sickle cell trait in semi-immune subjects altered the effect of CHMI on several B cells. In conclusion, lifelong but not vaccine exposure to malaria was associated with increased frequencies of multiple B cell subsets, with higher and lower percentages of CD1c and IgG expressing-cells, respectively. A single infection (CHMI) induces changes in B cell frequencies and is modulated by sickle cell trait and malaria-immunity status. Clinical Trials Registration NCT01624961, NCT02115516, and NCT02237586.

Selective IgM deficiency: evaluation of 75 patients according to different diagnostic criteria - Caroline Hamati Rosa Batista; Maria Carolina Martins Smanio; Pedro Borghesi Poltronieri; Leticia Leme Resende; Cristina Maria Kokron; Myrthes Toledo Barros; Rosana Camara Agondi; Natasha R. Ferraroni; Pérsio Roxo-Junior; Mariana Paes Leme Ferriani; Herberto Chong-Neto; Nelson Rosario Filho; et al. (Immunologic Research, 2025)

Highlighting the marine fungi Cunninghamella echinulata-9A5 as bioemulsifier for treating tannery leather residue - Mariana Bueno do Nascimento; Wanderson Zuza Cosme; Heber Eduardo Andrada; Kátia Roberta Prieto de Oliveira; Maria Isabela da Silva Figueiredo; Vanessa Mendes Rego; Marcos Antonio Soares; Rodrigo Sorrechia; Sarah Santana Sanchez; Rosemeire Cristina Linhari Rodrigue Pietro; Gustavo Muniz Dias; Marcio Luís Andrade e Silva; et al. (Brazilian Journal of Microbiology, 2025)

Current knowledge about per- and polyfluoroalkyl substances (PFAS) in the atmosphere: Fate, analytical methods and research priorities - Hellen Gonçalves Vieira; Maria Cristina Canela; Roberta Cerasi Urban; Benigno Sanchez Cabrero (Chemosphere, 2025)

Productive and welfare parameters in trimmed laying hens: A systematic review-meta-analysis - Henrique Sonda Gallina; Maria Eugênia Andrighetto Canozzi; Pietra Viertel Molinari; Juahil Martins de Oliveira Júnior; Ivan Bianchi; Fabiana Moreira; Débora Cristina Olsson; Paula Gabriela da Silva Pires; Javier Sanchez; Vanessa Peripolli (Research in Veterinary Science, 2025)

Linoleic acid induces migration and invasion through TLR4 in breast cancer cells - Kevin Perez Zaragoza; Rocio Castillo-Sanchez; Maria Sanchez-Juarez; Pedro Cortes-Reynosa; Eduardo Perez Salazar (Tissue and Cell, 2025)

Prescribed fire effects on vegetation responses in subtropical rangelands - Abmael S. Cardoso; Maria L. Silveira; Marta M. Kohmann; Joao M.B. Vendramini; João M.D. Sanchez; Namrata Ghimire; Rosvel Bracho (Rangelands, 2025)

The influence of diet, age, and obesity on hypothalamic omega-3 fatty acid transporter MFSD2a - Camila Venturini Ayres Cunha; Leandro Kansuke Oharomari; Julia Boro de Lima; Leticia Maria de Paula; Carlos Kiyoshi Katashima; Thaiane Rios; Talitha Meneguelli; Ana Paula Pinto; Danillo Henrique Travensolo Buoro; Fernanda da Silva Carneiro; Eduardo Ropelle; José Rodrigo Pauli; et al. (Food Research International, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Structural insights into ABA receptor agonists reveal critical features to optimize and design a broad-spectrum ABA signaling activator - Mar Bono; Cristian Mayordomo; Alberto Coego; Jonatan Illescas-Miranda; Maria Rivera-Moreno; Lourdes Infantes; Pablo López-Carracedo; Mayra Sanchez-Olvera; Constanza Martin-Vasquez; Gaston A. Pizzio; Javier Merino; Javier Forment; et al. (Molecular Plant, 2025)

Soft claims unwrapped: How they drive Preadolescents' food choices - Alazne Arraztio-Cordoba; Rafael A. Araque-Padilla; Cristian M. Olarte-Sanchez; Maria Jose Montero-Simo (Food Quality and Preference, 2025)

FTIR spectral signatures of Cretaceous-Paleogene sub-bituminous and bituminous coal: Insights into molecular structure evolution during coalification in the Eastern Cordillera Basin, Colombian Andes - Juan Sebastian Gomez-Neita; Ana Maria Pimentel Mizusaki; Taís Freitas da Silva; Sandra Rocio Manosalva-Sanchez; Jorge Eliecer Mariño-Martínez; David Enrique Vega Porras; Simone Patricia Aranha da Paz (International Journal of Coal Geology, 2025)

Toxicity and toxin profile of La Réunion (Indian Ocean) fish containing CTX-like compounds - Lourdes Barreiro-Crespo; Andres Sanchez-Henao; Sandra Gimeno-Monforte; Jaume Reverté; Mònica Campàs; Takeshi Tsumuraya; Jorge Diogène; Alina Tunin-Ley; Fanny Maillot; Cintia Flores; Núria Fontanals; Francesc Borrull; et al. (Harmful Algae, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Phylogenetically distant but cohabiting: Fungal communities of fine roots in Diphasiastrum complanatum, Pinus sylvestris, and Vaccinium myrtillus in a Lithuanian pine forest - Kristina Kuprina; Moana Wirth; Maria Sanchez Luque; Heike Heklau; Radvilė Rimgailė-Voicik; Manuela Bog; Martin Schnittler (Rhizosphere, 2025)

Attenuation of Cellular Senescence and Improvement of Osteogenic Differentiation Capacity of Human Liver Stem Cells Using Specific Senomorphic and Senolytic Agents - Allancer D. C. Nunes; Louise E. Pitcher; Henry A. Exner; Diego J. Grassi; Brittan Burns; Maria Beatriz Herrera Sanchez; Ciro Tetta; Giovanni Camussi; Paul D. Robbins (Stem Cell Reviews and Reports, 2025)
Expansion of adult stem cells in culture increases the percent of senescent cells, reduces their differentiation capacity and limits their clinical use. Here, we investigated whether treatment with certain senotherapeutic drugs would reduce the accumulation of senescent cells during expansion of human liver stem cells (HLSCs) while maintaining their differentiation capacity. Our results demonstrate that chronic treatment with the senomorphic XJB-5-131 or the senolytics cocktail D + Q reduced the number of senescent cells and significantly reduced the expression of senescence-associated genes and several inflammatory SASP factors in later passage HLSCs. Additionally, treatment with XJB-5-131 and D + Q improved the capacity of HLSCs to undergo osteogenic differentiation following extensive in vitro expansion. Overall, our data demonstrate that treatment with XJB-5-13 or D + Q results in a reduction in the percentage of replication-induced senescent HLSCs and likely other types of adult stem cells and improve the potential therapeutic use of later passage human stem cells. Graphical abstract

The effects of oral gestational particulate matter 10 exposure: Insights into neurodevelopmental milestones, inhibitory control, adult sociability, and object recognition - Diego Ruiz-Sobremazas; Mario Coca; Miguel Morales-Navas; Rocío Rodulfo-Cardenas; Caridad Lopez-Granero; Maria-Teresa Colomina; Cristian Perez-Fernandez; Fernando Sanchez-Santed (NeuroToxicology, 2025)

Rethinking evaporation measurement and modelling from inland waters − A discussion of the challenges to determine the actual values on the example of a shallow lowland reservoir - Uwe Spank; Matthias Koschorreck; Patrick Aurich; Ana Maria Sanchez Higuera; Armin Raabe; Peter Holstein; Christian Bernhofer; Matthias Mauder (Journal of Hydrology, 2025)

Tundra Plant Canopies Gradually Close Over Three Decades While Cryptogams Persist - Katlyn R. Betway‐May; William A. Gould; Sarah C. Elmendorf; Jeremy L. May; Robert D. Hollister; Steven F. Oberbauer; Amy Breen; Benjamin J. Crain; Ana Maria Sanchez Cuervo; Marilyn D. Walker; Donald A. Walker (Global Change Biology, 2025)
Global climate change phenomena are amplified in Arctic regions, driving rapid changes in the biota. Here, we examine changes in plant community structure over more than 30 years at two sites in arctic Alaska, USA, Imnavait Creek and Toolik Lake, to understand long‐term trends in tundra response to changing climate. Vegetation cover was sampled every 4–7 years on permanent 1 m 2 plots spanning a 1 km 2 grid using a point‐frame. The vascular plant canopies progressively closed at both locations. Canopy cover, defined here as an encounter of a vascular plant above the ground surface, increased from 63% to 91% at Imnavait Creek and from 63% to 89% at Toolik Lake. Both sites showed steady increases in maximum canopy height, increasing by approximately 50% (8 cm). While cover and height increased to some extent for all vascular plant growth forms, deciduous shrubs and graminoids changed the most. For example, at Imnavait Creek the cover of graminoids more than tripled (particularly in wet meadow plots), increasing by 237%. At Toolik Lake the cover of deciduous shrubs more than doubled (particularly in moist acidic plots), increasing by 145%. Despite the steady closing of the plant canopy, cryptogams (lichens and mosses) persisted; in fact, the cover of lichens increased. These results call into question the dominant dogma that cryptogams will decline with increases in vascular plant abundance and demonstrate the resilience of these understory plants. In addition to overall cover, the diversity of vascular plants increased at one site (Imnavait Creek). In contrast to much of the Arctic, summer air temperatures in the Toolik Lake region have not significantly increased over the 30+ year sampling period; however, winter temperatures increased substantially. Changes in vegetation community structure at Imnavait Creek and Toolik Lake are likely the result of winter warming.

NSSC: a neuro-symbolic AI system for enhancing accuracy of named entity recognition and linking from oncologic clinical notes - Álvaro García-Barragán; Ahmad Sakor; Maria-Esther Vidal; Ernestina Menasalvas; Juan Cristobal Sanchez Gonzalez; Mariano Provencio; Víctor Robles (Medical & Biological Engineering & Computing, 2025)
Accurate recognition and linking of oncologic entities in clinical notes is essential for extracting insights across cancer research, patient care, clinical decision-making, and treatment optimization. We present the Neuro-Symbolic System for Cancer (NSSC), a hybrid AI framework that integrates neurosymbolic methods with named entity recognition (NER) and entity linking (EL) to transform unstructured clinical notes into structured terms using medical vocabularies, with the Unified Medical Language System (UMLS) as a case study. NSSC was evaluated on a dataset of clinical notes from breast cancer patients, demonstrating significant improvements in the accuracy of both entity recognition and linking compared to state-of-the-art models. Specifically, NSSC achieved a 33% improvement over BioFalcon and a 58% improvement over scispaCy. By combining large language models (LLMs) with symbolic reasoning, NSSC improves the recognition and interoperability of oncologic entities, enabling seamless integration with existing biomedical knowledge. This approach marks a significant advancement in extracting meaningful information from clinical narratives, offering promising applications in cancer research and personalized patient care. Graphical abstract

Absence of genotoxic effects of high dietary levels of milk proteins associated or not with free or acylated lutein: An in vivo study using rats - Guilherme M. Tavares; Caroline Andolfato Sanchez; Mariana L. Rasera; Rosemar Sant'Anna dos Santos; Mariane Minussi Baptistella; Lusânia Maria Greggi Antunes (Food Bioscience, 2025)

In vivo anthelmintic activity of hydroethanolic extract of Piper cubeba fruits in sheep naturally infected with gastrointestinal nematodes - Clara de Araújo Sanchez; Juliana Alencar Gonçalves; Márcio Luís Andrade e Silva; Maria Gabriela Fontanetti Rodrigues; Fernanda Amorim Santos; Rosangela da Silva de Laurentiz; Ricardo Velludo Gomes de Soutello (Veterinary Parasitology, 2025)

Bench scale Layer-by-Layer microencapasulation of Lactiplantibacillus plantarum WCFS1 - Nelson Romano; Gina Tavares; Stéphanie Passot; Maria Guerrero Sanchez; Marina Golowczyc; Sonia Campoy; Fernanda Fonseca; Patrícia Alves; Patrícia Coimbra; Pedro Nuno Simões; Andrea Gomez-Zavaglia (Food Research International, 2025)

Bacterial communities forming yellow biofilms in different cave types share a common core - Tamara Martin-Pozas; Valme Jurado; Angel Fernandez-Cortes; Jose Maria Calaforra; Sergio Sanchez-Moral; Cesareo Saiz-Jimenez (Science of The Total Environment, 2024)

Improving ligilactobacillus salivarius CECT5713 freeze-dried stability through physical and biochemical characterization - Maria Guerrero Sanchez; Stephanie Passot; Monica Olivares; Fernanda Fonseca (Cryobiology, 2024)

Prospecting for New Potential Biocontrol Agents Against Colletotrichum lindemuthianum, the Causal Agent of Bean Anthracnose - Rosilene C. Matos; Sibele A. da Silva; Isabella F. Cordeiro; Angélica B. Sanchez; Maria R. A. Damasceno; Lorrana C. M. Rocha; Gustavo S. Kajitani; Josino José Barbosa; Marisa V. de Queiroz; Camila Carrião Machado Garcia; Leandro M. Moreira (Journal of Soil Science and Plant Nutrition, 2024)

The Impact of Perfluorooctanoic Acid (PFOA) on the Mussel Mytilus galloprovincialis: A Multi-Biomarker Evaluation - Sandra Copeto; Sara Ganço; Inês João Ferreira; Didier Sanchez; Maria João Nunes; Carla Motta; Marco Silva; Mário Diniz (Oceans, 2024)
Perfluorooctanoic acid (PFOA) has been widely studied due to its environmental persistence and bioaccumulation potential, raising concerns about its effects on aquatic life. This research evaluates the impact of PFOA on the antioxidant defenses and stress response systems of the mussel Mytilus galloprovincialis. Mussels were exposed to three concentrations of PFOA (1, 10, and 100 µg·L−1) over 28 days. Several biomarkers, including glutathione S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), lipid peroxidation (LPO), total antioxidant capacity (TAC), vitellogenin (VTG), ubiquitin (UBI), and caspase-3 (CASP) were analyzed. The results suggest stress responses, particularly in animals exposed to higher concentrations, as shown by GST and SOD activities which increased according to PFOA concentrations. Additionally, oxidative stress markers such as MDA and CAT showed variable responses depending on the exposure concentration tested. This study underscores the need for further investigation into the effects of PFOA on mollusks but also the need to unveil gender-specific responses in aquatic organisms exposed to this contaminant. The concentrations of PFOA used in our research are lower than those examined in previous studies, providing crucial insights into the impacts of even minimal exposure levels. It highlights the potential of M. galloprovincialis as a bioindicator in environmental monitoring programs, providing crucial insights for environmental management and policymaking regarding regulating and monitoring PFOA in marine settings. Consequently, in a country where seafood consumption is the second largest in Europe, implementing environmental policies and regulatory measures to manage and monitor PFOA levels in marine environments is crucial.

Chemical composition and in vitro iron bioavailability of extruded and open-pan cooked germinated and ungerminated pearl whole millet “Pennisetum glaucum (L.) R. Br.” - Jaqueline Maciel Vieira Theodoro; Mariana Grancieri; Livya Alves Oliveira; Ceres Mattos Della Lucia; Izabela Maria Montezano de Carvalho; Felipe Sanchez Bragagnolo; Mauricio Ariel Rostagno; Raymond P. Glahn; Carlos Wanderlei Piler Carvalho; Bárbara Pereira da Silva; Hércia Stampini Duarte Martino (Food Chemistry, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effect of spinal cord injury on the skin temperature of different regions of interest during a graded exercise test in a moderate temperature environment - Jose Luis Sanchez-Jimenez; Rosa M. Cibrian-Ortiz de Anda; Maria Vazquez-Fariñas; Soraya Martin-Manjarres; Jose Ignacio Priego-Quesada; Inmaculada Aparicio-Aparicio (Journal of Thermal Biology, 2024)

Assessment of low impact development (LID) strategies under different land uses in an urban sub-catchment in the Philippines - Cheamson Garret K. Boongaling; Janice B. Sevilla-Nastor; Maria Victoria O. Espaldon; Patricia Ann J. Sanchez; Jessica D. Villanueva-Peyraube; Karen Ann B. Jago-on (Journal of Environmental Management, 2024)

Unveiling novel contrasting photosynthetic responses in Medicago truncatula under combined drought stress and Phoma medicaginis infection - Nourhene Maiza; Wiem Mnafgui; Cheima Jabri; Fethia Zribi; Walid Zorrig; Ndiko Ludidi; Maria Teresa Sanchez-Ballesta; Mounawer Badri (Plant Biosystems, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Regional foraging areas of green turtles (Chelonia mydas) nesting at Aldabra Atoll: insights from stable isotopes and satellite telemetry - Cheryl L. Sanchez; Paolo Casale; Nancy Bunbury; Luke A’Bear; Maria Bielsa; Christopher W. Jones; Martin C. van Rooyen; Brian Souyana; Frauke Fleischer-Dogley; Simona A. Ceriani (Biodiversity and Conservation, 2024)
Sea turtles spend the majority of their lives at foraging grounds. These areas are important for population persistence but generally occur in coastal habitats, which are under increasing human pressure. Identifying key foraging areas is therefore an important step to understanding critical sea turtle habitats, and therefore their threats. Isotope ratios ( δ 15 N, δ 13 C) from skin tissues of 90 green turtles ( Chelonia mydas ) nesting at the regionally important rookery of Aldabra Atoll, Seychelles, were analyzed with samples collected during two periods: 51 samples from March to September 2021, and 39 samples from January to April 2022. These analyses were complemented by nine satellite tracks to identify key foraging areas. Hierarchical clustering and discriminant function analysis identified two main foraging areas: the East African coast (Tanzania and Somalia) and northern Madagascar. Isotopic values indicated that the majority of green turtles nesting at Aldabra forage at one of these two areas, with slightly more green turtles visiting the East African coast. Geographical isotopic patterns were not found latitudinally, suggesting a potential limit to this approach for coastal areas in the Western Indian Ocean. However, we found longitudinal variation of δ 13 C and δ 15 N that few studies have reported. This is the first study in this region to combine satellite telemetry and stable isotope analysis to assign likely foraging areas of green turtles and advances understanding of the complex migration patterns and foraging ecology of this species. We demonstrate the potential and the limitations of stable isotope analysis for identifying/characterizing green turtle foraging areas in this region.

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

Association between dietary (poly)phenol intake and the ATHLOS Healthy Ageing Scale in the Polish arm of the HAPIEE study - Urszula Stepaniak; Giuseppe Grosso; Maciej Polak; Barbara Gradowicz-Prajsnar; Magdalena Kozela; Martin Bobak; Albert Sanchez-Niubo; Denes Stefler; Josep Maria Haro; Andrzej Pająk (GeroScience, 2024)
Inverse association between (poly)phenol intake and age-related disorders has been demonstrated; however, little is known whether they affect comprehensively assessed healthy aging. The aim of this study was to evaluate the associations between the intake of (poly)phenol (including selected classes and subclasses) and healthy aging scores related to biopsychosocial aspects of health and functioning. A cross-sectional study was performed using data on 9774 randomly selected citizens of Krakow (Poland) who were 45–69 years of age. Dietary (poly)phenol intake was evaluated using a food frequency questionnaire and matching food consumption data with the Phenol-Explorer database. The healthy aging scores were estimated from the ATHLOS Healthy Ageing Scale (HAS) developed by the Ageing Trajectories of Health-Longitudinal Opportunities and Synergies (ATHLOS) consortium. Beta coefficients were calculated using multivariable linear regression models. In multivariable adjusted models, there were significant positive associations between the ATHLOS HAS score and intake of total (poly)phenols ( b per increase of 100 mg/day = 0.081; 95% CI, 0.050; 0.112) and among main classes of (poly)phenols with phenolic acids ( b = 0.139; 95% CI, 0.098; 0.180). Intake of remaining classes of (poly)phenols (flavonoids, lignans, stilbenes, and others) was not related to the ATHLOS HAS score. Among individual classes studied, hydroxycinnamic acids, flavonols, flavones, and dihydrochalcones were associated with better healthy aging. The findings suggest the beneficial effect of total dietary (poly)phenol and some classes and subclasses of (poly)phenol intake in terms of healthy aging in Poland. These findings should be confirmed in other settings and with prospective data.

Fine-scale foraging ecology and habitat use of sympatric green and hawksbill turtles in the Western Indian ocean - Cheryl L. Sanchez; Paolo Casale; Nancy Bunbury; Luke A'Bear; Veronique Banane; Frances Benstrong; Maria Bielsa; Christopher W. Jones; Anna Koester; Susan Murasko; Martin C. van Rooyen; Frauke Fleischer-Dogley; et al. (Marine Environmental Research, 2024)

Detection of intrathecal IgG antibody for varicella and measles diagnosis by evaluation and comparison of a commercial IgG chemiluminescent immunoassay with two ELISAs - Rafael Garcia; Maria Jiménez-Valera; Daniel Ruiz-Buck; Carlos Sanchez; Almudena Rojas; Malte Hendrik Schütz; Jose Rojas; Klaus - Peter Hunfeld (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Correction: Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2024)

Effects of crotamine in human prostate cancer cell line - João Victor Alberghini-dos-Santos; Caroline Andolfato Sanchez; Karla de Castro Figueiredo Bordon; Manuela Berto Pucca; Lusânia Maria Greggi Antunes; Eliane Candiani Arantes; Isadora Sousa de Oliveira (Toxicon, 2024)

Plastic pollution transcends marine protected area boundaries in the eastern tropical and south-eastern Pacific - Zara L.R. Botterell; Francisca Ribeiro; Daniela Alarcón-Ruales; Eliana Alfaro; Joanna Alfaro-Shigueto; Nicola Allan; Nicole Becerra; Laura Braunholtz; Susana Cardenas-Diaz; Diamela de Veer; Gabriela Escobar-Sanchez; Maria Virginia Gabela-Flores; et al. (Marine Pollution Bulletin, 2024)

Adaptive response of prokaryotic communities to extreme pollution flooding in a Paleolithic rock art cave (Pindal Cave, northern Spain) - Tamara Martin-Pozas; Soledad Cuezva; Angel Fernandez-Cortes; Maria Gonzalez-Pumariega; Javier Elez; Elsa Duarte; Marco de la Rasilla; Juan Carlos Canaveras; Cesareo Saiz-Jimenez; Sergio Sanchez-Moral (Science of The Total Environment, 2024)

A biophysical suitability model to identify best areas for the cultivation of potential cash crops: The case of basil in Valle del Cauca - Maria del Mar Esponda-Bernal; Andrés Fernando Echeverri-Sanchez; Eduar Fernando Aguirre-Gonzalez; Robert Santiago Andrade (Agricultural Systems, 2024)

ULTRAPETALAs in action: Unraveling their role in root development - Diego Ornelas-Ayala; Carlos Cortés-Quiñones; J. Arturo Arciniega-González; Adriana Garay-Arroyo; Berenice García-Ponce; Elena R. Alvarez-Buylla; Maria De La Paz Sanchez (Plant Science, 2024)

Experimental CIGS technology performance under low concentration photovoltaic conditions - Miguel Barragán Sánchez-Lanuza; Isidoro Lillo-Bravo; Sara Moreno-Tejera; J.L. Sancho Rodríguez; Jose-Maria Delgado-Sanchez (Journal of Cleaner Production, 2024)

Neurodevelopmental consequences of gestational exposure to particulate matter 10: Ultrasonic vocalizations and gene expression analysis using a bayesian approach - Diego Ruiz-Sobremazas; Mario Ruiz Coca; Miguel Morales-Navas; Rocío Rodulfo-Cárdenas; Caridad López-Granero; Maria Teresa Colomina; Cristian Perez-Fernandez; Fernando Sanchez-Santed (Environmental Research, 2024)

Late Pleistocene–Holocene multi-decadal patterns of extreme floods in NW Iberia: The Duero River palaeoflood record - Gerardo Benito; Noam Greenbaum; Alicia Medialdea; Mikel Calle; Yolanda Sanchez-Moya; Maria Machado; Juan Antonio Ballesteros-Cánovas; Juan Pablo Corella (Quaternary Science Reviews, 2023)

Preferential expression of SCN1A in GABAergic neurons improves survival and epileptic phenotype in a mouse model of Dravet syndrome - Ana Ricobaraza; Maria Bunuales; Manuela Gonzalez-Aparicio; Saja Fadila; Moran Rubinstein; Irene Vides-Urrestarazu; Julliana Banderas; Noemi Sola-Sevilla; Rocio Sanchez-Carpintero; Jose Luis Lanciego; Elvira Roda; Adriana Honrubia; et al. (Journal of Molecular Medicine, 2023)
The SCN1A gene encodes the alpha subunit of a voltage-gated sodium channel (Na v 1.1), which is essential for the function of inhibitory neurons in the brain. Mutations in this gene cause severe encephalopathies such as Dravet syndrome (DS). Upregulation of SCN1A expression by different approaches has demonstrated promising therapeutic effects in preclinical models of DS. Limiting the effect to inhibitory neurons may contribute to the restoration of brain homeostasis, increasing the safety and efficacy of the treatment. In this work, we have evaluated different approaches to obtain preferential expression of the full SCN1A cDNA (6 Kb) in GABAergic neurons, using high-capacity adenoviral vectors (HC-AdV). In order to favour infection of these cells, we considered ErbB4 as a surface target. Incorporation of the EGF-like domain from neuregulin 1 alpha (NRG1α) in the fiber of adenovirus capsid allowed preferential infection in cells lines expressing ErbB4. However, it had no impact on the infectivity of the vector in primary cultures or in vivo. For transcriptional control of transgene expression, we developed a regulatory sequence (DP3V) based on the Distal-less homolog enhancer ( Dlx ), the vesicular GABA transporter ( VGAT ) promoter, and a portion of the SCN1A gene. The hybrid DP3V promoter allowed preferential expression of transgenes in GABAergic neurons both in vitro and in vivo. A new HC-AdV expressing SCN1A under the control of this promoter showed improved survival and amelioration of the epileptic phenotype in a DS mouse model. These results increase the repertoire of gene therapy vectors for the treatment of DS and indicate a new avenue for the refinement of gene supplementation in this disease. Key messages Adenoviral vectors can deliver the SCN1A cDNA and are amenable for targeting. An adenoviral vector displaying an ErbB4 ligand in the capsid does not target GABAergic neurons. A hybrid promoter allows preferential expression of transgenes in GABAergic neurons. Preferential expression of SCN1A in GABAergic cells is therapeutic in a Dravet syndrome model.

Editorial: Climate change impacts on Mediterranean coastal and transitional areas: assessment, projection, and adaptation - Davide Bonaldo; Agustin Sanchez-Arcilla; Achilleas G. Samaras; Maria Snoussi (Frontiers in Marine Science, 2023)

Potentially toxic element bioaccumulation in consumed indoor shrimp farming associated with diet, water and sediment levels - José Joaquín Ramos-Miras; Maria Jose Sanchez-Muros; Patricio Renteria; Carlos Gil de Carrasco; Luis Roca-Perez; Mireia Boluda-Navarro; Javier Pro; Jose Antonio Rodríguez Martín (Environmental Science and Pollution Research, 2023)
Shrimp production is an important industry for many countries and shrimp consumption is increasing worldwide. Shrimps are a highly nutritional food, but can pose a risk for human health if subject to high levels of environmental contaminants. This work studies the presence of As, Cd, Co, Cr, Cu, Hg, Ni, Pb and Zn in shrimps from Ecuador and compares them to such contents noted in other shrimp-production areas in the world to evaluate the possible risks associated with these elements for consumer health, and to relate them to potentially toxic element (PTE) contents in water, sediments and diets, and also to animal biometric parameters. The PTE levels (mg kg −1 DM) obtained are as follows: in the head—As (3.52–6.11), Cd (0.02–0.10), Co (0.14–0.49) Cr (0.23–4.89), Cu (99.9––233.0), Ni (0.52–1.86), Pb (0.24–1.09), Zn (51.8–100.5) and Hg (μg kg −1 DM) (10.00–66.81); in the tail—(0.91–3.21), Cd (0.01–0.02), Co (0.01–0.43) Cr (0.01–6.52), Cu (20.0–72.44), Ni (0.15–2.03), Pb (0.01–0.69), Zn (31.2–66.1) and Hg (μg kg −1 DM) (10.00–67.18). The concentration of all the PTEs is generally lower than the limits set for seafood by European regulations, except for As in the cephalothorax (4.63 mg kg −1 ). Different behaviours for PTE accumulation in shrimps were found, which preferentially tend to accumulate in the cephalothorax, except for Hg (40.13 μg kg −1 DM), which accumulates in muscle (body) and is associated with contents of proteins, lipids and total shrimp weight. Nonetheless, the target hazard quotient (THQ) values for PTEs indicate that the consumption of shrimp muscles from Ecuador does not pose a human health risk because the values of these indices are below 1 in all cases.

Ketorolac removal through photoelectrocatalysis using TiO2 nanotubes in water system - Sebastián Oyarzabal Rodríguez; Luis Erick Coy-Aceves; Jesus Eduardo Daniel Morales; Jose Luis Sanchez-Salas; Carlos Alberto Martínez-Huitle; Milena Maria Ramirez-Rodrigues; Monica Cerro-Lopez (Environmental Science and Pollution Research, 2023)

Phenotyping genotypic performance under multistress conditions: Mediterranean wheat as a case study - Jose Luis Araus; Fatima Zahra Rezzouk; Rut Sanchez-Bragado; Nieves Aparicio; Maria Dolores Serret (Field Crops Research, 2023)

Marine Isotope Stage 4 (71–57 ka) on the Western European margin: Insights to the drainage and dynamics of the Western European Ice Sheet - Samuel Toucanne; Teresa Rodrigues; Guillemette Menot; Guillaume Soulet; Sandrine Cheron; Isabelle Billy; Frederique Eynaud; Pierre Antoine; Jaap S. Sinninghe Damste; Edouard Bard; Maria-Fernanda Sanchez Goñi (Global and Planetary Change, 2023)

Impacts of coral bleaching on reef fish abundance, biomass and assemblage structure at remote Aldabra Atoll, Seychelles: insights from two survey methods - Anna Koester; Cesc Gordó−Vilaseca; Nancy Bunbury; Sebastian C. A. Ferse; Amanda Ford; Philip Haupt; Luke A’Bear; Maria Bielsa; April Jasmine Burt; Jake Letori; Emma Mederic; Ella Nancy; et al. (Frontiers in Marine Science, 2023)
Introduction Coral bleaching immediately impacts the reef benthos, but effects on fish communities are less well understood because they are often delayed and confounded by anthropogenic interactions. Methods We assessed changes in fish abundance, biomass and community composition before and after the 2015/16 coral bleaching event at Aldabra Atoll, Seychelles, where local human impacts are minimal, but reefs suffered 50% bleaching-induced coral mortality. We monitored 12 shallow (2–5 m water depth) and nine deep (15 m water depth) permanent survey sites using two survey methods: indicator surveys recording 84 taxa over six years (pre-: 2014; post-bleaching: 2016–2019, 2021), sizing fish based on six size-class categories, and extended fish surveys recording 198 taxa over two years (pre-: 2015; post-bleaching: 2020) with size estimates to the nearest cm (excluding fish < 8 cm). Results During indicator surveys, mean fish abundance did not change on deep reefs. However, abundance increased by 77% on shallow reefs between 2014 and 2016, which was mainly driven by increases in herbivores and omnivores, likely as a response to elevated turf algae cover following coral mortality. Overall (and functional group-specific) indicator fish biomass did not differ between 2014 and 2016 and remained at or above pre-bleaching levels throughout 2016–2021. In contrast, extended fish surveys in 2015 and 2020 showed a 55–60% reduction in overall abundance on shallow and deep reefs, and a 69% reduction in biomass on shallow reefs, with decreases in biomass occurring in all functional groups. Biomass on deep reefs did not differ between 2015 and 2020. Multivariate analysis of both data sets revealed immediate and long-lasting differences between pre- and post-bleaching fish community compositions, driven largely by herbivorous, omnivorous and piscivorous taxa. Discussion Results from the indicator surveys suggest that the bleaching event had limited impact on fish abundance and biomass, while the extended surveys recorded changes in abundance and biomass which would otherwise have gone undetected. Our findings improve understanding of the shift a broad community of fish undergoes following a mass coral bleaching event and highlights the value of survey methods that include the full suite of species to detect ecological responses to environmental drivers.

The bovine leukemia virus infection prolongs immunosuppression in dairy cows during the periparturient period by sustaining higher expression of immunological checkpoints in T cells - Alice Maria Melo do Nascimento; Carolina Menezes Suassuna de Souza; Ana Claudia Dumont Oliveira; Maiara Garcia Blagitz; Eduardo Milton Ramos Sanchez; Alice Maria Melville Paiva Della Libera; Ricardo de Miranda Henriques Leite; Artur Cezar de Carvalho Fernandes; Fernando Nogueira Souza (Veterinary Immunology and Immunopathology, 2023)

Insights into the mechanisms of L. salivarius CECT5713 resistance to freeze-dried storage - Maria Guerrero Sanchez; Stéphanie Passot; Sarrah Ghorbal; Sonia Campoy; Monica Olivares; Fernanda Fonseca (Cryobiology, 2023)

Tick-Borne Pathogens Screening Using a Multiplex Real-Time Polymerase Chain Reaction-Based Method - Sergio Andres Cardenas-Cadena; Maria Eugenia Castañeda-Lopez; Fabiana Esther Mollinedo-Montaño; Sodel Vazquez-Reyes; Jorge Lara-Arias; Ivan Alberto Marino-Martinez; Iram Pablo Rodriguez-Sanchez; Idalia Garza-Veloz; Margarita L. Martinez-Fierro (Acta Parasitologica, 2023)
Purpose This study aims to develop and evaluate a cost-effective, user-friendly multiplex quantitative real-time polymerase chain reaction (qPCR) method for detecting multiple tick-borne pathogens associated with human and veterinary diseases. Methods In silico PCR was performed to design and evaluate primer sequences reported for amplifying Rickettsia spp ., Borrelia spp. , and Ehrlichia spp. Single and multiplex qPCR assays were then standardized to detect individual pathogens and multiple pathogens in a single reaction. Positive controls were generated to determine the dynamic range of the methods. In the validation phase, a total of 800 samples were screened for the presence of tick-borne pathogens. Results Identification in a single qPCR reaction (multiplex) of Ehrlichia spp . , and Borrelia spp. with a limit of detection of 10 copies and Rickettsia spp . with 100 copies, a PCR efficiency (E) of 90–100% and a coefficient of correlation ( R 2 ) of 0.998–0.996 for all pathogens. Conclusion The ability to detect three significant pathogens (Ehrlichia spp ., Rickettsia spp ., and Borrelia spp .) in a single qPCR reaction offers a significant advantage in the field of molecular diagnostics for tick-borne diseases. This advancement has a profound impact on public health as it facilitates the selection of appropriate treatment protocols, thereby reducing complications associated with disease progression. The streamlined approach provided by this method simplifies the diagnostic process and enables timely intervention, ultimately improving patient outcomes and mitigating the potential risks associated with untreated or misdiagnosed tick-borne infections.

The role of water in reactions catalysed by hydrolases under conditions of molecular crowding - Maria A. Perillo; Inés Burgos; Eduardo M. Clop; Julieta M. Sanchez; Verónica Nolan (Biophysical Reviews, 2023)

Profile of calls and activities of the first Teratogen Information Service in Latin America through 32 years - Lavínia Schuler-Faccini; Maria Teresa V. Sanseverino; Sacha Krolow e Silva; Camila P. Barbosa; Danton S. Ordovás; Carolina S. Arashiro; Ricardo Rohweder; Ana Paula Ornaghi; Filipe M. Sanchez; Giulia Radin; Victoria L.S. Gomes; Lucas M. Pires; et al. (Neurotoxicology and Teratology, 2023)

Acute physiological responses to a pyramidal exercise protocol and the associations with skin temperature variation in different body areas - Barlo Hillen; Daniel Andrés López; Joaquín Martín Marzano-Felisatti; José Luis Sanchez-Jimenez; Rosa Maria Cibrián Ortiz de Anda; Markus Nägele; Maria Rosario Salvador-Palmer; Pedro Pérez-Soriano; Elmar Schömer; Perikles Simon; Jose Ignacio Priego-Quesada (Journal of Thermal Biology, 2023)

A State-of-the-Science Review on Metal Biomarkers - Irene Martinez-Morata; Marisa Sobel; Maria Tellez-Plaza; Ana Navas-Acien; Caitlin G. Howe; Tiffany R. Sanchez (Current Environmental Health Reports, 2023)

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Exploring the production of antioxidants and biogas from avocado (Persea Americana var. Americana) residues as an alternative for developing rural bioeconomies - Maria Camila Garcia-Vallejo; Juan Camilo Solarte-Toro; Mariana Ortiz-Sanchez; Leonardo Chamorro-Anaya; Lina Chamorro-Anaya; Pavel Peroza-Piñeres; Alexander Pérez-Cordero; Carlos Ariel Cardona Alzate (Sustainable Chemistry and Pharmacy, 2023)

Proteomic characterization of eight-day-old equine blastocysts produced in vivo - Antonio Carlos Albuquerque Teles Filho; Maria Julia Bezerra; Deisy Johana Diaz Sanchez; José Cordeiro Araújo Neto; Maria Eduarda Magalhães Souza; Jander Fabrício Costa; Arabela Guedes de Azevedo Viana; Aline Araújo Martins; Mauricio Valle Souza; Wagner Fontes; Carlos André Ornelas Ricart; Fábio Roger Vasconcelos; et al. (Journal of Equine Veterinary Science, 2023)

Nutritional composition, ultrastructural characterization, and peptidome profile of antioxidant hemp protein hydrolysates - Sergio Montserrat-de la Paz; Fernando Rivero-Pino; Alvaro Villanueva; Rocio Toscano-Sanchez; Maria E. Martin; Francisco Millan; Maria C. Millan-Linares (Food Bioscience, 2023)

Bi-functional photocatalytic heterostructures combining titania thin films with carbon quantum dots (C-QDs/TiO2) for effective elimination of water pollutants - Pinelopi P. Falara; Islam Ibrahim; Adamantia Zourou; Labrini Sygellou; David Emanuel Sanchez; George Em. Romanos; Lida Givalou; Maria Antoniadou; Michalis K. Arfanis; Changseok Han; Mauricio Terrones; Konstantinos V. Kordatos (Environmental Science and Pollution Research, 2023)
In this study, carbon quantum dots (C-QDs), prepared via hydrothermal-microwave procedures, were successfully combined with nanostructured titania (TiO 2 ). The photocatalytic oxidation/reduction activity of the C-QDs/TiO 2 composite films was evaluated in the decomposition of organic-inorganic contaminants from aqueous solutions under UV illumination. Physicochemical characterizations were applied to investigate the crystal structure of the carbon quantum dots and the composites. It was found that the prepared C-QDs/TiO 2 composites had great contribution to the photocatalytic reduction of hexavalent chromium (Cr +6 ) species and 4-Nitrophenol (PNP) as well as to the photocatalytic oxidation of methylene blue (MB) and Rhodamine B (RhB) dyes. The mechanism of the photocatalytic reaction was studied with trapping experiments, revealing that the electron (e − ) radical species were powerfully supported for the photocatalytic reduction of Cr +6 and PNP and the holes ( h + ) are the main active species for the photocatalytic oxidation reactions.

Rivers as corridors for gene flow of the neotropical bamboo Guadua velutina - Maria de la Luz Perez-Garcia; Jessica Pérez-Alquicira; Yessica Rico; Ofelia Vargas-Ponce; Eduardo Ruiz-Sanchez (Aquatic Botany, 2023)

Surface, satellite ozone variations in Northern South America during low anthropogenic emission conditions: a machine learning approach - Alejandro Casallas; Maria Paula Castillo-Camacho; Edwin Ricardo Sanchez; Yuri González; Nathalia Celis; Juan Felipe Mendez-Espinosa; Luis Carlos Belalcazar; Camilo Ferro (Air Quality, Atmosphere & Health, 2023)

Natural radioactivity in European drinking water: A review - Marta Gómez; Siiri Suursoo; Nicolas Martin-Sanchez; Taavi Vaasma; Maria Leier (Critical Reviews in Environmental Science and Technology, 2023)

Monocyte-to-Lymphocyte Ratio in Clot Analysis as a Marker of Cardioembolic Stroke Etiology - Jesús Juega; Carlos Palacio-Garcia; Maite Rodriguez; Matias Deck; David Rodriguez-Luna; Manuel Requena; Álvaro García-Tornel; Noelia Rodriguez-Villatoro; Marta Rubiera; Sandra Boned; Marian Muchada; Marc Ribo; et al. (Translational Stroke Research, 2022)

Application of Anodic Oxidation in Diazinon Degradation - Tayanara Menezes Santos; Maria Nogueira Marques; Odelsia Leonor Sanchez de Alsina; Maria Eliana Camargo Ferreira; Natália Ueda Yamaguchi; Rosângela Bergamasco; Eliane Bezerra Cavalcanti (Water, Air, & Soil Pollution, 2022)

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Downscaling UAV land surface temperature using a coupled wavelet-machine learning-optimization algorithm and its impact on evapotranspiration - Mahyar Aboutalebi; Alfonso F. Torres-Rua; Mac McKee; William P. Kustas; Hector Nieto; Maria Mar Alsina; Alex White; John H. Prueger; Lynn McKee; Joseph Alfieri; Lawrence Hipps; Calvin Coopmans; et al. (Irrigation Science, 2022)

LAI estimation across California vineyards using sUAS multi-seasonal multi-spectral, thermal, and elevation information and machine learning - Rui Gao; Alfonso F. Torres-Rua; Mahyar Aboutalebi; William A. White; Martha Anderson; William P. Kustas; Nurit Agam; Maria Mar Alsina; Joseph Alfieri; Lawrence Hipps; Nick Dokoozlian; Hector Nieto; et al. (Irrigation Science, 2022)

Time-series clustering of remote sensing retrievals for defining management zones in a vineyard - Noa Ohana-Levi; Feng Gao; Kyle Knipper; William P. Kustas; Martha C. Anderson; Maria del Mar Alsina; Luis A. Sanchez; Arnon Karnieli (Irrigation Science, 2022)

Circulating concentrations of free triiodothyronine are associated with central adiposity and cardiometabolic risk factors in young euthyroid adults - Elisa Merchan-Ramirez; Guillermo Sanchez-Delgado; Cristina Arrizabalaga-Arriazu; Francisco M Acosta; Maria Jose Arias-Tellez; Manuel Muñoz-Torres; Jose V Garcia-Lario; Jose M Llamas-Elvira; Jonatan R Ruiz (Journal of Physiology and Biochemistry, 2022)
Thyroid dysfunction is associated with classic cardiometabolic risk factors in humans. However, this relationship remains unclear in young euthyroid adults. The present work examines the associations of circulating thyroid hormones (THs) and thyroid-stimulating hormone (TSH) concentrations with body composition and cardiometabolic risk factors in young euthyroid adults. A total of 106 sedentary, euthyroid adults (72 women; 22 ± 2 years old) participated in this cross-sectional study. THs and TSH serum concentrations were determined in fasting conditions (6 h). Body composition (fat mass (FM), lean mass (LM), and visceral adipose tissue (VAT)) was determined by dual-energy X-ray absorptiometry, anthropometric parameters (weight, height, and waist circumference) were measured, and neck adipose tissue mass was quantified through computed tomography (CT) scanning. Cardiometabolic risk factors including fasting glucose and lipid metabolism markers, hepatic phosphatase and transaminases, and blood pressure were also assessed. Free triiodothyronine (FT3) concentration was positively associated with body mass index, LM, VAT, and waist circumference (all P ≤ 0.038). FT3 was also associated with glucose, insulin, HOMA-IR, fatty liver index, and blood pressure (all P < 0.024). All the associations were attenuated when adjusting for sex. In contrast, we found no associations of TSH or free thyroxine with any body composition parameter or cardiometabolic risk factors. In conclusion, FT3 is associated with central adiposity and cardiometabolic risk factors including insulin resistance, fatty liver index, and mean, systolic and diastolic blood pressure in young euthyroid adults. ClinicalTrials.gov identifier: NCT02365129.

The Neuroprotective Lipocalin Apolipoprotein D Stably Interacts with Specific Subtypes of Detergent-Resistant Membrane Domains in a Basigin-Independent Manner - Miriam Corraliza-Gomez; Manuela del Caño-Espinel; Diego Sanchez; Maria D. Ganfornina (Molecular Neurobiology, 2022)
Accumulated evidence points to the lipocalin apolipoprotein D (ApoD), one of the few genes consistently upregulated upon brain ageing and neurodegeneration, as an endogenous controller of the redox state of cellular and extracellular lipid structures. This biochemical function has downstream consequences as apparently varied as control of glycocalyx and myelin compaction, cell viability upon oxidative stress or modulation of signalling pathways. In spite of this knowledge, it is still unclear if ApoD function requires canonical receptor-mediated transductions systems. This work aims to examine ApoD-cell membrane interaction and its dependence on a proposed ApoD receptor, Basigin. Whole and fractionated membrane preparations from the brain, primary astrocytes, glial and neuronal cell lines, reveal ApoD as a very specific component of particular subtypes of detergent-resistant microdomains (DRMs). ApoD interacts in vitro with neuronal membranes and is stably associated with astrocytic membranes. ApoD associates with DRMs with specific buoyancy properties that co-fractionate with plasma or late-endosome-lysosome markers. A mass spectrometry analysis reveals that these Triton X-114 DRMs contain both plasma membrane and endosomal-lysosomal compartment lipid raft proteins. ApoD-DRM association is maintained under metabolic and acute oxidative stress conditions. However, ApoD-membrane interaction, its internalization and its lipid-antioxidant function do not require the presence of Basigin. This work supports a stable association of ApoD with membranes, independent of Basigin, and provides the basis to fully understand ApoD antioxidant neuroprotective mechanism as a mechanism taking place in specific membrane subdomains.

Correction to: Early dysfunction of functional connectivity in healthy elderly with subjective memory complaints - Ricardo Bajo; Nazareth P. Castellanos; Maria Eugenia López; José María Ruiz-Sanchez de Leon; Pedro Montejo; Mercedes Montenegro; Marcos Llanero; Pedro Gil; Raquel Yubero; Evgenia Baykova; Nuria Paul; Sara Aurtenetxe; et al. (GeroScience, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Membrane lipids and maximum lifespan in clownfish - Pedro F. Almaida-Pagan; Alejandro Lucas-Sanchez; Antonio Martinez-Nicolas; Eva Terzibasi; Maria Angeles Rol de Lama; Alessandro Cellerino; Pilar Mendiola; Jorge de Costa (Fish Physiology and Biochemistry, 2022)
The longevity-homeoviscous adaptation (LHA) theory of ageing states that lipid composition of cell membranes is linked to metabolic rate and lifespan, which has been widely shown in mammals and birds but not sufficiently in fish. In this study, two species of the genus Amphiprion ( Amphiprion percula and Amphiprion clarkii , with estimated maximum lifespan potentials [MLSP] of 30 and 9–16 years, respectively) and the damselfish Chromis viridis (estimated MLSP of 1–2 years) were chosen to test the LHA theory of ageing in a potential model of exceptional longevity. Brain, livers and samples of skeletal muscle were collected for lipid analyses and integral part in the computation of membrane peroxidation indexes (PIn) from phospholipid (PL) fractions and PL fatty acid composition. When only the two Amphiprion species were compared, results pointed to the existence of a negative correlation between membrane PIn value and maximum lifespan, well in line with the predictions from the LHA theory of ageing. Nevertheless, contradictory data were obtained when the two Amphiprion species were compared to the shorter-lived C. viridis . These results along with those obtained in previous studies on fish denote that the magnitude (and sometimes the direction) of the differences observed in membrane lipid composition and peroxidation index with MLSP cannot explain alone the diversity in longevity found among fishes.

Efficacy of high-intensity interval- or continuous aerobic-training on insulin resistance and muscle function in adults with metabolic syndrome: a clinical trial - Jaime Gallo-Villegas; Leonardo A. Castro-Valencia; Laura Pérez; Daniel Restrepo; Oscar Guerrero; Sergio Cardona; Yeliana L. Sánchez; Manuela Yepes-Calderón; Luis H. Valbuena; Miguel Peña; Andrés F. Milán; Maria C. Trillos-Almanza; et al. (European Journal of Applied Physiology, 2022)

Environmental and economic analysis of bioethanol production from sugarcane molasses and agave juice - Maria Magdalena Parascanu; Nestor Sanchez; Fabiola Sandoval-Salas; Carlos Mendez Carreto; Gabriela Soreanu; Luz Sanchez-Silva (Environmental Science and Pollution Research, 2021)
In this article, sugarcane molasses and agave juice were compared as potential feedstocks for producing bioethanol in Mexico in terms of their environmental impact and economic factors. Life cycle assessment (LCA) using SimaPro was carried out to calculate environmental impacts by using a cradle-to-gate approach. A preliminary economic analysis was performed to determine the economic feasibility of the studied options. Also, capital goods costs were obtained using the Aspen Plus economy package. Moreover, a sensitivity analysis was involved to compare the environmental and economic viability of producing bioethanol from sugarcane molasses and agave juice. LCA results revealed that cultivation and fermentation were the most harmful stages when producing bioethanol from sugarcane molasses and agave juice, respectively. Furthermore, when it was derived from agave juice rather than sugarcane molasses, it had more environmental benefits. This was ascribed to the lower consumption rate of fertilizers, pesticides, and emissions given off from the former. Regarding financial aspects, the preliminary analysis showed that producing bioethanol was not economically viable when grid energy alone was used. However, if power from the grid is partially replaced with renewable energy, producing bioethanol becomes economically feasible, and sugarcane molasses is the most suitable feedstock. Graphical abstract

Potential negative effects of the Green Wall on Sahel's biodiversity - Marisa Naia; Pedro Tarroso; Andack Saad Sow; André Vicente Liz; Duarte Vasconcelos Gonçalves; Fernando Martínez‐Freiría; Frederico Santarém; Gholam Hosein Yusefi; Guillermo Velo‐Antón; Ignazio Avella; Jeffrey O. Hanson; Leili Khalatbari; et al. (Conservation Biology, 2021)

Incidence, clinical characteristics, risk factors and outcomes of meningoencephalitis in patients with COVID-19 - Marcos Fragiel; Òscar Miró; Pere Llorens; Sònia Jiménez; Pascual Piñera Salmerón; Guillermo Burillo-Putze; Alfonso Martín; Francisco Javier Martín-Sánchez; Eric Jorge García Lamberechts; Javier Jacob; Aitor Alquézar-Arbé; Ferran Llopis-Roca; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Enzyme Activities as Indicators of Soil Quality: Response to Intensive Soybean and Rice Crops - Andrés M. Attademo; Juan C. Sanchez-Hernandez; Rafael C. Lajmanovich; Maria Rosa Repetti; Paola M. Peltzer (Water, Air, & Soil Pollution, 2021)

Exome sequencing reveals predominantly de novo variants in disorders with intellectual disability (ID) in the founder population of Finland - Irma Järvelä; Tuomo Määttä; Anushree Acharya; Juha Leppälä; Shalini N. Jhangiani; Maria Arvio; Auli Siren; Minna Kankuri-Tammilehto; Hannaleena Kokkonen; Maarit Palomäki; Teppo Varilo; Mary Fang; et al. (Human Genetics, 2021)
The genetics of autosomal recessive intellectual disability (ARID) has mainly been studied in consanguineous families, however, founder populations may also be of interest to study intellectual disability (ID) and the contribution of ARID. Here, we used a genotype-driven approach to study the genetic landscape of ID in the founder population of Finland. A total of 39 families with syndromic and non-syndromic ID were analyzed using exome sequencing, which revealed a variant in a known ID gene in 27 families. Notably, 75% of these variants in known ID genes were de novo or suspected de novo (64% autosomal dominant; 11% X-linked) and 25% were inherited (14% autosomal recessive; 7% X-linked; and 4% autosomal dominant). A dual molecular diagnosis was suggested in two families (5%). Via additional analysis and molecular testing, we identified three cases with an abnormal molecular karyotype, including chr21q22.12q22.2 uniparental disomy with a mosaic interstitial 2.7 Mb deletion covering DYRK1A and KCNJ6. Overall, a pathogenic or likely pathogenic variant was identified in 64% (25/39) of the families. Last, we report an alternate inheritance model for 3 known ID genes ( UBA7 , DDX47 , DHX58 ) and discuss potential candidate genes for ID, including SYPL1 and ERGIC3 with homozygous founder variants and de novo variants in POLR2F and DNAH3. In summary, similar to other European populations, de novo variants were the most common variants underlying ID in the studied Finnish population, with limited contribution of ARID to ID etiology, though mainly driven by founder and potential founder variation in the latter case.

Multidimensional Proteomic Approach of Endothelial Progenitors Demonstrate Expression of KDR Restricted to CD19 Cells - Coralie L. Guerin; Léa Guyonnet; Guillaume Goudot; Dominique Revets; Maria Konstantinou; Anna Chipont; Richard Chocron; Adeline Blandinieres; Lina Khider; Jeanne Rancic; Christophe Peronino; Benjamin Debuc; et al. (Stem Cell Reviews and Reports, 2021)

Nosocomial infections associated to COVID-19 in the intensive care unit: clinical characteristics and outcome - Tommaso Bardi; Vicente Pintado; Maria Gomez-Rojo; Rosa Escudero-Sanchez; Amal Azzam Lopez; Yolanda Diez-Remesal; Nilda Martinez Castro; Patricia Ruiz-Garbajosa; David Pestaña (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Use of metakaolin or coal gangue as a partial substitution of cement in mechanical performance of PC mortars - Mauricio Arreola Sanchez; Hugo Luis Chavez Garcia; Wilfrido Martinez Molina; Elia Mercedes Alonso Guzman; Andres Antonio Torres Acosta; José Maria Ponce Ortega (European Journal of Environmental and Civil Engineering, 2021)

Genetic modifiers and phenotypic variability in neuromuscular disorders - Magdalena Mroczek; Maria Gabriela Sanchez (Journal of Applied Genetics, 2020)

X-ray tomography of cryopreserved human prostate cancer cells: mitochondrial targeting by an organoiridium photosensitiser - Elizabeth M. Bolitho; Carlos Sanchez-Cano; Huaiyi Huang; Ian Hands-Portman; Matthew Spink; Paul D. Quinn; Maria Harkiolaki; Peter J. Sadler (JBIC Journal of Biological Inorganic Chemistry, 2020)
The organoiridium complex Ir[(C,N) 2 (O,O)] ( 1 ) where C, N = 1-phenylisoquinoline and O,O = 2,2,6,6-tetramethyl-3,5-heptanedionate is a promising photosensitiser for Photo-Dynamic Therapy (PDT). 1 is not toxic to cells in the dark. However, irradiation of the compound with one-photon blue or two-photon red light generates high levels of singlet oxygen ( 1 O 2 ) (in Zhang et al. Angew Chem Int Ed Engl 56 (47):14898-14902 10.1002/anie.201709082,2017 ), both within cell monolayers and in tumour models. Moreover, photo-excited 1 oxidises key proteins, causing metabolic alterations in cancer cells with potent antiproliferative activity. Here, the tomograms obtained by cryo-Soft X-ray Tomography (cryo-SXT) of human PC3 prostate cancer cells treated with 1 , irradiated with blue light, and cryopreserved to maintain them in their native state, reveal that irradiation causes extensive and specific alterations to mitochondria, but not other cellular components. Such new insights into the effect of 1 O 2 generation during PDT using iridium photosensitisers on cells contribute to a detailed understanding of their cellular mode of action. Graphic abstract

Intrahepatic Administration of Human Liver Stem Cells in Infants with Inherited Neonatal-Onset Hyperammonemia: A Phase I Study - Marco Spada; Francesco Porta; Dorico Righi; Carlo Gazzera; Francesco Tandoi; Ivana Ferrero; Franca Fagioli; Maria Beatriz Herrera Sanchez; Pier Luigi Calvo; Elisa Biamino; Stefania Bruno; Monica Gunetti; et al. (Stem Cell Reviews and Reports, 2020)
Previous studies have shown that human liver stem-like cells (HLSCs) may undergo differentiation in vitro into urea producing hepatocytes and in vivo may sustain liver function in models of experimentally induced acute liver injury. The aim of this study was to assess the safety of HLSCs intrahepatic administration in inherited neonatal-onset hyperammonemia. The study was approved by the Agenzia Italiana del Farmaco on favorable opinion of the Italian Institute of Health as an open-label, prospective, uncontrolled, monocentric Phase I study (HLSC 01–11, EudraCT-No. 2012–002120-33). Three patients affected by argininosuccinic aciduria (patient 1) and methylmalonic acidemia (patients 2 and 3) and included in the liver transplantation list were enrolled. In all patients, HLSCs were administered by percutaneous intrahepatic injections (once a week for two consecutive weeks) within the first months of life. The first patient received 125,000 HLSCs x gram of liver/dose while the other two patients received twice this dose. No immunosuppression was administered since HLSCs possess immunomodulatory activities. None of the patients experienced infections, hyperammonemia decompensation, or other adverse events during the whole observation period. No donor specific antibodies (DSA) against HLSCs were detected. Patients were metabolic stable despite an increase (~30%) in protein intake. Two patients underwent liver transplantation after 19 and 11 months respectively, and after explantation, the native livers showed no histological alterations. In conclusion, percutaneous intrahepatic administration of HLSCs was safe in newborn with inherited neonatal-onset hyperammonemia. These data pave the way for Phase II studies in selected inherited and acquired liver disorders.

Altered Neocortical Dynamics in a Mouse Model of Williams–Beuren Syndrome - Miguel Dasilva; Alvaro Navarro-Guzman; Paula Ortiz-Romero; Alessandra Camassa; Alberto Muñoz-Cespedes; Victoria Campuzano; Maria V. Sanchez-Vives (Molecular Neurobiology, 2020)

Blood Flow-Restricted Training in Older Adults: A Narrative Review - Abel Plaza-Florido; Jairo H. Migueles; Antonio Piepoli; Pablo Molina-Garcia; Maria Rodriguez-Ayllon; Cristina Cadenas-Sanchez; Jose Mora-Gonzalez; Irene Esteban-Cornejo; Francisco B. Ortega (Journal of Science in Sport and Exercise, 2020)

A Data-Driven Multi-scale Technique for fMRI Mapping of the Human Somatosensory Cortex - Selene Da Rocha Amaral; Rosa Maria Sanchez Panchuelo; Susan Francis (Brain Topography, 2020)

Correction to: Progress on bringing together raptor collections in Europe for contaminant research and monitoring in relation to chemicals regulation - Paola Movalli; Guy Duke; Gloria Ramello; René Dekker; Al Vrezec; Richard F. Shore; Antonio García-Fernández; Chris Wernham; Oliver Krone; Nikiforos Alygizakis; Alexander Badry; Fausto Barbagli; et al. (Environmental Science and Pollution Research, 2019)

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Identification and pathogenicity of Phytophthora species in pear commercial orchards in Argentina - Aixa Daihana Sanchez; María Cristina Sosa; María Cecilia Lutz; Gastón Alejandro Carreño; Maria Julia Ousset; Gabriela Susana Lucero (European Journal of Plant Pathology, 2019)

Progress on bringing together raptor collections in Europe for contaminant research and monitoring in relation to chemicals regulation - Paola Movalli; Guy Duke; Gloria Ramello; René Dekker; Al Vrezec; Richard F. Shore; Antonio García-Fernández; Chris Wernham; Oliver Krone; Nikiforos Alygizakis; Alexander Badry; Fausto Barbagli; et al. (Environmental Science and Pollution Research, 2019)

Woody vegetation dynamics in the tropical and subtropical Andes from 2001 to 2014: Satellite image interpretation and expert validation - T. Mitchell Aide; H. Ricardo Grau; Jordan Graesser; Maria Jose Andrade‐Nuñez; Ezequiel Aráoz; Ana P. Barros; Marconi Campos‐Cerqueira; Eulogio Chacon‐Moreno; Francisco Cuesta; Raul Espinoza; Manuel Peralvo; Molly H. Polk; et al. (Global Change Biology, 2019)
The interactions between climate and land‐use change are dictating the distribution of flora and fauna and reshuffling biotic community composition around the world. Tropical mountains are particularly sensitive because they often have a high human population density, a long history of agriculture, range‐restricted species, and high‐beta diversity due to a steep elevation gradient. Here we evaluated the change in distribution of woody vegetation in the tropical Andes of South America for the period 2001–2014. For the analyses we created annual land‐cover/land‐use maps using MODIS satellite data at 250 m pixel resolution, calculated the cover of woody vegetation (trees and shrubs) in 9,274 hexagons of 115.47 km 2 , and then determined if there was a statistically significant ( p n = 479) lost forests and 63.4% ( n = 829) gained forests. We estimated an overall net gain of ~500,000 ha in woody vegetation. Forest loss dominated the 1,000–1,499 m elevation zone and forest gain dominated above 1,500 m. The most important transitions were forest loss at lower elevations for pastures and croplands, forest gain in abandoned pastures and cropland in mid‐elevation areas, and shrub encroachment into highland grasslands. Expert validation confirmed the observed trends, but some areas of apparent forest gain were associated with new shade coffee, pine, or eucalypt plantations. In addition, after controlling for elevation and country, forest gain was associated with a decline in the rural population. Although we document an overall gain in forest cover, the recent reversal of forest gains in Colombia demonstrates that these coupled natural‐human systems are highly dynamic and there is an urgent need of a regional real‐time land‐use, biodiversity, and ecosystem services monitoring network.

Evapotranspiration estimates derived using thermal-based satellite remote sensing and data fusion for irrigation management in California vineyards - Kyle R. Knipper; William P. Kustas; Martha C. Anderson; Joseph G. Alfieri; John H. Prueger; Christopher R. Hain; Feng Gao; Yun Yang; Lynn G. McKee; Hector Nieto; Lawrence E. Hipps; Maria Mar Alsina; et al. (Irrigation Science, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2019)
Cerebral preconditioning (PC) confers endogenous brain protection after stroke. Ischemic stroke patients with a prior transient ischemic attack (TIA) may potentially be in a preconditioned state. Although PC has been associated with the activation of pro-survival signals, the mechanism by which preconditioning confers neuroprotection is not yet fully clarified. Recently, we have described that PC-mediated neuroprotection against ischemic insult is promoted by p53 destabilization, which is mediated by its main regulator MDM2. Moreover, we have previously described that the human Tp53 Arg72Pro single nucleotide polymorphism (SNP) controls susceptibility to ischemia-induced neuronal apoptosis and governs the functional outcome of patients after stroke. Here, we studied the contribution of the human Tp53 Arg72Pro SNP on PC-induced neuroprotection after ischemia. Our results showed that cortical neurons expressing the Pro72-p53 variant exhibited higher PC-mediated neuroprotection as compared with Arg72-p53 neurons. PC prevented ischemia-induced nuclear and cytosolic p53 stabilization in Pro72-p53 neurons. However, PC failed to prevent mitochondrial p53 stabilization, which occurs in Arg72-p53 neurons after ischemia. Furthermore, PC promoted neuroprotection against ischemia by controlling the p53/active caspase-3 pathway in Pro72-p53, but not in Arg72-p53 neurons. Finally, we found that good prognosis associated to TIA within 1 month prior to ischemic stroke was restricted to patients harboring the Pro72 allele. Our findings demonstrate that the Tp53 Arg72Pro SNP controls PC-promoted neuroprotection against a subsequent ischemic insult by modulating mitochondrial p53 stabilization and then modulates TIA-induced ischemic tolerance.

Chemosensitization of hepatocellular carcinoma cells to sorafenib by β-caryophyllene oxide-induced inhibition of ABC export pumps - Silvia Di Giacomo; Oscar Briz; Maria J. Monte; Laura Sanchez-Vicente; Lorena Abete; Elisa Lozano; Gabriela Mazzanti; Antonella Di Sotto; Jose J. G. Marin (Archives of Toxicology, 2019)

Age-related changes in mitochondrial membrane composition of Nothobranchius furzeri.: comparison with a longer-living Nothobranchius species - Pedro F. Almaida-Pagan; Carmen Ortega-Sabater; Alejandro Lucas-Sanchez; Daniel Gonzalez-Silvera; Antonio Martinez-Nicolas; Maria Angeles Rol de Lama; Pilar Mendiola; Jorge de Costa (Biogerontology, 2019)

Isotopic evidence for the reconstruction of diet and mobility during village formation in the Early Middle Ages: Las Gobas (Burgos, northern Spain) - Iranzu Guede; Luis Angel Ortega; Maria Cruz Zuluaga; Ainhoa Alonso-Olazabal; Xabier Murelaga; José Luis Solaun; Iban Sanchez; Agustín Azkarate (Archaeological and Anthropological Sciences, 2018)

Maximum Influent Salinity Affects the Diversity of Mineral-Precipitation-Mediating Bacterial Communities in Membrane Biofilm of Hybrid Moving Bed Biofilm Reactor-Membrane Bioreactor - Alejandro Rodriguez-Sanchez; Barbara Muñoz-Palazon; Miguel Hurtado-Martinez; Maria Angustias Rivadeneyra; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Water, Air, & Soil Pollution, 2018)

First report of Pseudomicrostroma juglandis (syn. Microstroma juglandis) causing downy leaf spot of walnut in Argentina - Maria Cecilia Lutz; Aixa Daihana Sanchez; Lucas Vera; Ana Gabriela Scarso; Maria Cristina Sosa (Journal of Plant Pathology, 2018)

Trace analysis of parabens preservatives in drinking water treatment sludge, treated, and mineral water samples - Ana Victoria Marta-Sanchez; Sergiane Souza Caldas; Antunielle Schneider; Sónia Maria Vaz Sanches Cardoso; Ednei Gilberto Primel (Environmental Science and Pollution Research, 2018)

Characterization and cancer risk assessment of VOCs in home and school environments in gran La Plata, Argentina - Jorge Esteban Colman Lerner; Maria de los Angeles Gutierrez; Daniela Mellado; Daniela Giuliani; Laura Massolo; Erica Yanina Sanchez; Andres Porta (Environmental Science and Pollution Research, 2018)

An Italian tomato “Cuore di Bue” case study: challenges and benefits using subcategory assessment method for social life cycle assessment - Luigia Petti; Paola Karina Sanchez Ramirez; Marzia Traverso; Cassia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2018)

Exposure and risk analysis to particulate matter, metals, and polycyclic aromatic hydrocarbon at different workplaces in Argentina - Jorge Esteban Colman Lerner; Maria Lucila Elordi; Marcos Agustin Orte; Daniela Giuliani; Maria de los Angeles Gutierrez; EricaYanina Sanchez; Jorge Enrique Sambeth; Atilio Andres Porta (Environmental Science and Pollution Research, 2018)

Erratum to: Historical analysis of interannual rainfall variability and trends in southeastern Brazil based on observational and remotely sensed data - Isela L. Vásquez P.; Lígia Maria Nascimento de Araujo; Luiz Carlos Baldicero Molion; Mariana de Araujo Abdalad; Daniel Medeiros Moreira; Arturo Sanchez; Humberto Alves Barbosa; Otto Corrêa Rotunno Filho (Climate Dynamics, 2018)

Historical analysis of interannual rainfall variability and trends in southeastern Brazil based on observational and remotely sensed data - Isela L. Vásquez P.; Lígia Maria Nascimento de Araujo; Luiz Carlos Baldicero Molion; Mariana de Araujo Abdalad; Daniel Medeiros Moreira; Arturo Sanchez; Humberto Alves Barbosa; Otto Corrêa Rotunno Filho (Climate Dynamics, 2018)

Urine metabolomics insight into acute kidney injury point to oxidative stress disruptions in energy generation and H2S availability - Marta Martin-Lorenzo; Laura Gonzalez-Calero; Angeles Ramos-Barron; Maria D. Sanchez-Niño; Carlos Gomez-Alamillo; Juan Manuel García-Segura; Alberto Ortiz; Manuel Arias; Fernando Vivanco; Gloria Alvarez-Llamas (Journal of Molecular Medicine, 2017)

Identifying Toxic Impacts of Metals Potentially Released during Deep-Sea Mining—A Synthesis of the Challenges to Quantifying Risk - Chris Hauton; Alastair Brown; Sven Thatje; Nélia C. Mestre; Maria J. Bebianno; Inês Martins; Raul Bettencourt; Miquel Canals; Anna Sanchez-Vidal; Bruce Shillito; Juliette Ravaux; Magali Zbinden; et al. (Frontiers in Marine Science, 2017)

Diversity, distribution and dynamics of full-length Copia and Gypsy LTR retroelements in Solanum lycopersicum - Rosalía Cristina Paz; Melisa Eliana Kozaczek; Hernán Guillermo Rosli; Natalia Pilar Andino; Maria Virginia Sanchez-Puerta (Genetica, 2017)

Plasma miR-34a-5p and miR-545-3p as Early Biomarkers of Alzheimer’s Disease: Potential and Limitations - Marta Cosín-Tomás; Anna Antonell; Albert Lladó; Daniel Alcolea; Juan Fortea; Mario Ezquerra; Albert Lleó; Maria José Martí; Mercè Pallàs; Raquel Sanchez-Valle; José Luís Molinuevo; Coral Sanfeliu; et al. (Molecular Neurobiology, 2017)

Protective Effect of the Sulfated Agaran Isolated from the Red Seaweed Laurencia aldingensis Against Toxic Effects of the Venom of the Snake, Lachesis muta - Ana Cláudia Rodrigues da Silva; Luciana Garcia Ferreira; Maria Eugênia Rabello Duarte; Mutue Toyota Fujii; Eladio Flores Sanchez; Miguel Daniel Noseda; André Lopes Fuly (Marine Biotechnology, 2016)

Global genetic diversity of Aedes aegypti - Andrea Gloria‐Soria; Diego Ayala; Ambicadutt Bheecarry; Olger Calderon‐Arguedas; Dave D. Chadee; Marina Chiappero; Maureen Coetzee; Khouaildi Bin Elahee; Ildefonso Fernandez‐Salas; Hany A. Kamal; Basile Kamgang; Emad I. M. Khater; et al. (Molecular Ecology, 2016)
Mosquitoes, especially Aedes aegypti , are becoming important models for studying invasion biology. We characterized genetic variation at 12 microsatellite loci in 79 populations of Ae. aegypti from 30 countries in six continents, and used them to infer historical and modern patterns of invasion. Our results support the two subspecies Ae. aegypti formosus and Ae. aegypti aegypti as genetically distinct units. Ae. aegypti aegypti populations outside Africa are derived from ancestral African populations and are monophyletic. The two subspecies co‐occur in both East Africa (Kenya) and West Africa (Senegal). In rural/forest settings (Rabai District of Kenya), the two subspecies remain genetically distinct, whereas in urban settings, they introgress freely. Populations outside Africa are highly genetically structured likely due to a combination of recent founder effects, discrete discontinuous habitats and low migration rates. Ancestral populations in sub‐Saharan Africa are less genetically structured, as are the populations in Asia. Introduction of Ae. aegypti to the New World coinciding with trans‐Atlantic shipping in the 16th to 18th centuries was followed by its introduction to Asia in the late 19th century from the New World or from now extinct populations in the Mediterranean Basin. Aedes mascarensis is a genetically distinct sister species to Ae. aegypti s.l. This study provides a reference database of genetic diversity that can be used to determine the likely origin of new introductions that occur regularly for this invasive species. The genetic uniqueness of many populations and regions has important implications for attempts to control Ae. aegypti , especially for the methods using genetic modification of populations.

Optimal Immobilization of Acidic Proteases from Monterey Sardine ( Sardinops sagax caeurelea ) on Partially Deacetylated Chitin from Shrimp Head Waste - Jesus Aaron Salazar-Leyva; Jaime Lizardi-Mendoza; Juan Carlos Ramirez-Suarez; Elisa Miriam Valenzuela-Soto; Josafat Marina Ezquerra-Brauer; Francisco Javier Castillo-Yañez; Maria Elena Lugo-Sanchez; Guillermina Garcia-Sanchez; Maria Gisela Carvallo-Ruiz; Ramon Pacheco-Aguilar (Journal of Aquatic Food Product Technology, 2016)

Variability and trends of downward surface global solar radiation over the Iberian Peninsula based on ERA ‐40 reanalysis - João Carlos Perdigão; Rui Salgado; Maria João Costa; Hari Prasad Dasari; Arturo Sanchez‐Lorenzo (International Journal of Climatology, 2016)
A climate study of the incidence of downward surface global solar radiation ( SSRD ) in the Iberian Peninsula ( IP ) based primarily on ERA ‐40 reanalysis is presented. NCEP / NCAR reanalysis and ground‐based records from several Portuguese and Spanish stations have been also considered. The results show that reanalysis can capture a similar inter‐annual variability as compared to ground‐based observations, especially on a monthly basis, even though annual ERA ‐40 ( NCEP / NCAR ) values tend to underestimate (overestimate) the observations with a mean relative difference of around 20 W m –2 (40 W m –2 ). On the other hand, ground‐based measurements in Portuguese stations during the period 1964–1989 show a tendency to decrease until the mid‐1970s followed by an increase up to the end of the study period, in line with the dimming/brightening phenomenon reported in the literature. Nevertheless, there are different temporal behaviours as a greater increase since the 1970s is observed in the south and less industrialized regions. Similarly, the ERA ‐40 reanalysis shows a noticeable decrease until the early 1970s followed by a slight increase up to the end of the 1990s, suggesting a dimming/brightening transition around the early 1970s, earlier in the south and centre and later in the north of the IP . Although there are slight differences in the magnitude of the trends as well as the turning year of the dimming/brightening periods, the decadal changes of ERA ‐40 fairly agree with the ground‐based observations in Portugal and Spain, in contrast to most of the literature for other regions of the world, and is used in the climatology of the SSRD in the study area. NCEP / NCAR reanalysis does not capture the decadal variations of SSRD in the IP . The results show that part of the decadal variability of the global radiation in the IP is related to changes in cloud cover (represented in ERA ‐40).

The revisited genome of Pseudomonas putida KT2440 enlightens its value as a robust metabolic chassis - Eugeni Belda; Ruben G. A. van Heck; Maria José Lopez‐Sanchez; Stéphane Cruveiller; Valérie Barbe; Claire Fraser; Hans‐Peter Klenk; Jörn Petersen; Anne Morgat; Pablo I. Nikel; David Vallenet; Zoé Rouy; et al. (Environmental Microbiology, 2016)
Summary By the time the complete genome sequence of the soil bacterium Pseudomonas putida KT2440 was published in 2002 (Nelson et al ., ) this bacterium was considered a potential agent for environmental bioremediation of industrial waste and a good colonizer of the rhizosphere. However, neither the annotation tools available at that time nor the scarcely available omics data—let alone metabolic modeling and other nowadays common systems biology approaches—allowed them to anticipate the astonishing capacities that are encoded in the genetic complement of this unique microorganism. In this work we have adopted a suite of state‐of‐the‐art genomic analysis tools to revisit the functional and metabolic information encoded in the chromosomal sequence of strain KT2440. We identified 242 new protein‐coding genes and re‐annotated the functions of 1548 genes, which are linked to almost 4900 PubMed references. Catabolic pathways for 92 compounds (carbon, nitrogen and phosphorus sources) that could not be accommodated by the previously constructed metabolic models were also predicted. The resulting examination not only accounts for some of the known stress tolerance traits known in P. putida but also recognizes the capacity of this bacterium to perform difficult redox reactions, thereby multiplying its value as a platform microorganism for industrial biotechnology.

Impact of methionine on a partial-nitritation biofilter - Alejandro Gonzalez-Martinez; Alejandro Rodriguez-Sanchez; Maria Jesus Garcia-Ruiz; Francisco Osorio; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2016)

Subcategory assessment method for social life cycle assessment. Part 2: application in Natura’s cocoa soap - Paola Karina Sanchez Ramirez; Luigia Petti; Fabien Brones; Cássia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2016)

Ovarian activity and estrus behavior in early postpartum cows grazing Leucaena leucocephala in the tropics - Maria Bottini-Luzardo; Carlos Aguilar-Perez; Fernando Centurion-Castro; Francisco Solorio-Sanchez; Armin Ayala-Burgos; Ruben Montes-Perez; David Muñoz-Rodriguez; Juan Ku-Vera (Tropical Animal Health and Production, 2015)

Towards a framework for assessment and management of cumulative human impacts on marine food webs - Sylvaine Giakoumi; Benjamin S. Halpern; Loïc N. Michel; Sylvie Gobert; Maria Sini; Charles‐François Boudouresque; Maria‐Cristina Gambi; Stelios Katsanevakis; Pierre Lejeune; Monica Montefalcone; Gerard Pergent; Christine Pergent‐Martini; et al. (Conservation Biology, 2015)
Effective ecosystem‐based management requires understanding ecosystem responses to multiple human threats, rather than focusing on single threats. To understand ecosystem responses to anthropogenic threats holistically, it is necessary to know how threats affect different components within ecosystems and ultimately alter ecosystem functioning. We used a case study of a Mediterranean seagrass (Posidonia oceanica) food web and expert knowledge elicitation in an application of the initial steps of a framework for assessment of cumulative human impacts on food webs. We produced a conceptual seagrass food web model, determined the main trophic relationships, identified the main threats to the food web components, and assessed the components’ vulnerability to those threats. Some threats had high (e.g., coastal infrastructure) or low impacts (e.g., agricultural runoff) on all food web components, whereas others (e.g., introduced carnivores) had very different impacts on each component. Partitioning the ecosystem into its components enabled us to identify threats previously overlooked and to reevaluate the importance of threats commonly perceived as major. By incorporating this understanding of system vulnerability with data on changes in the state of each threat (e.g., decreasing domestic pollution and increasing fishing) into a food web model, managers may be better able to estimate and predict cumulative human impacts on ecosystems and to prioritize conservation actions.

The Contribution of Agriculture, Forestry and other Land Use activities to Global Warming, 1990–2012 - Francesco N. Tubiello; Mirella Salvatore; Alessandro F. Ferrara; Jo House; Sandro Federici; Simone Rossi; Riccardo Biancalani; Rocio D. Condor Golec; Heather Jacobs; Alessandro Flammini; Paolo Prosperi; Paola Cardenas‐Galindo; et al. (Global Change Biology, 2015)
We refine the information available through the IPCC AR 5 with regard to recent trends in global GHG emissions from agriculture, forestry and other land uses ( AFOLU ), including global emission updates to 2012. Using all three available AFOLU datasets employed for analysis in the IPCC AR 5, rather than just one as done in the IPCC AR 5 WGIII Summary for Policy Makers, our analyses point to a down‐revision of global AFOLU shares of total anthropogenic emissions, while providing important additional information on subsectoral trends. Our findings confirm that the share of AFOLU emissions to the anthropogenic total declined over time. They indicate a decadal average of 28.7 ± 1.5% in the 1990s and 23.6 ± 2.1% in the 2000s and an annual value of 21.2 ± 1.5% in 2010. The IPCC AR 5 had indicated a 24% share in 2010. In contrast to previous decades, when emissions from land use (land use, land use change and forestry, including deforestation) were significantly larger than those from agriculture (crop and livestock production), in 2010 agriculture was the larger component, contributing 11.2 ± 0.4% of total GHG emissions, compared to 10.0 ± 1.2% of the land use sector. Deforestation was responsible for only 8% of total anthropogenic emissions in 2010, compared to 12% in the 1990s. Since 2010, the last year assessed by the IPCC AR 5, new FAO estimates indicate that land use emissions have remained stable, at about 4.8 Gt CO 2 eq yr −1 in 2012. Emissions minus removals have also remained stable, at 3.2 Gt CO 2 eq yr −1 in 2012. By contrast, agriculture emissions have continued to grow, at roughly 1% annually, and remained larger than the land use sector, reaching 5.4 Gt CO 2 eq yr −1 in 2012. These results are useful to further inform the current climate policy debate on land use, suggesting that more efforts and resources should be directed to further explore options for mitigation in agriculture, much in line with the large efforts devoted to REDD+ in the past decade.

A Basal Tone of 2-Arachidonoylglycerol Contributes to Early Oligodendrocyte Progenitor Proliferation by Activating Phosphatidylinositol 3-Kinase (PI3K)/AKT and the Mammalian Target of Rapamycin (MTOR) Pathways - Oscar Gomez; Maria A. Sanchez-Rodriguez; Silvia Ortega-Gutierrez; Henar Vazquez-Villa; Carmen Guaza; Francisco Molina-Holgado; Eduardo Molina-Holgado (Journal of Neuroimmune Pharmacology, 2015)

CXCL10/XCL1 fusokine elicits in vitro and in vivo chemotaxis - Yessica E. Sanchez-Lugo; Jose J. Perez-Trujillo; Yolanda Gutierrez-Puente; Aracely Garcia-Garcia; Humberto Rodriguez-Rocha; Oralia Barboza-Quintana; Gerardo E. Muñoz-Maldonado; Odila Saucedo-Cardenas; Roberto Montes de Oca-Luna; Maria J. Loera-Arias (Biotechnology Letters, 2015)

Sustained Increase of PKA Activity in the Postcommissural Putamen of Dyskinetic Monkeys - Garikoitz Azkona; Irene Marcilla; Rakel López de Maturana; Amaya Sousa; Esther Pérez-Navarro; Maria-Rosario Luquin; Rosario Sanchez-Pernaute (Molecular Neurobiology, 2014)

Subcategory assessment method for social life cycle assessment. Part 1: methodological framework - Paola Karina Sanchez Ramirez; Luigia Petti; Nara Tudela Haberland; Cássia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2014)

Shorebird low spillover risk of mosquito-borne pathogens on Iberian wetlands - Sara Pardal; José A. Alves; Líbia Zé-Zé; Hugo Osório; Afonso Rocha; Ricardo J. Lopes; Pete Potts; Fátima Amaro; Francisco Santiago-Quesada; Juan M. Sanchez-Guzman; José Masero; Maria J. Alves; et al. (Journal of Ornithology, 2014)

3,4-DGE is cytotoxic and decreases HSP27/HSPB1 in podocytes - Maria Dolores Sanchez-Niño; Jonay Poveda; Ana Belen Sanz; Susana Carrasco; Marta Ruiz-Ortega; Rafael Selgas; Jesus Egido; Alberto Ortiz (Archives of Toxicology, 2013)

Haplotype diversity generated by ancient recombination-like events in the MHC of Indian rhesus macaques - Gaby G. M. Doxiadis; Nanine de Groot; Nel Otting; Annemiek J. M. de Vos-Rouweler; Maria J. Bolijn; Corrine M. C. Heijmans; Natasja G. de Groot; Marit K. H. van der Wiel; Edmond J. Remarque; Christelle Vangenot; José M. Nunes; Alicia Sanchez-Mazas; et al. (Immunogenetics, 2013)

Local Understandings of Conservation in Southeastern Mexico and Their Implications for Community‐Based Conservation as an Alternative Paradigm - VICTORIA REYES‐GARCIA; ISABEL RUIZ‐MALLEN; LUCIANA PORTER‐BOLLAND; EDUARDO GARCIA‐FRAPOLLI; EDWARD A. ELLIS; MARIA‐ELENA MENDEZ; DIANA J. PRITCHARD; MARÍA‐CONSUELO SANCHEZ‐GONZALEZ (Conservation Biology, 2013)
Since the 1990s national and international programs have aimed to legitimize local conservation initiatives that might provide an alternative to the formal systems of state‐managed or otherwise externally driven protected areas. We used discourse analysis (130 semistructured interviews with key informants) and descriptive statistics (679 surveys) to compare local perceptions of and experiences with state‐driven versus community‐driven conservation initiatives. We conducted our research in 6 communities in southeastern Mexico. Formalization of local conservation initiatives did not seem to be based on local knowledge and practices. Although interviewees thought community‐based initiatives generated less conflict than state‐managed conservation initiatives, the community‐based initiatives conformed to the biodiversity conservation paradigm that emphasizes restricted use of and access to resources. This restrictive approach to community‐based conservation in Mexico, promoted through state and international conservation organizations, increased the area of protected land and had local support but was not built on locally relevant and multifunctional landscapes, a model that community‐based conservation is assumed to advance. Percepciones Locales de Conservación en el Sureste de México e Implicaciones para la Conservación Comunitaria como Paradigma Alternativo

Effects of Acute Sodium Fluoride Exposure on Kidney Function, Water Homeostasis, and Renal Handling of Calcium and Inorganic Phosphate - Mitzi Paola Santoyo-Sanchez; Maria del Carmen Silva-Lucero; Laura Arreola-Mendoza; Olivier Christophe Barbier (Biological Trace Element Research, 2013)

Delineation of specific management areas for coffee cultivation based on the soil–relief relationship and numerical classification - Maria Gabriela Baracat Sanchez; José Marques; Diego Silva Siqueira; Livia Arantes Camargo; Gener Tadeu Pereira (Precision Agriculture, 2013)

Virtual reality for assessment of patients suffering chronic pain: a case study - Joan Llobera; Mar González-Franco; Daniel Perez-Marcos; Josep Valls-Solé; Mel Slater; Maria V. Sanchez-Vives (Experimental Brain Research, 2013)

Is my hand connected to my body? The impact of body continuity and arm alignment on the virtual hand illusion - Daniel Perez-Marcos; Maria V. Sanchez-Vives; Mel Slater (Cognitive Neurodynamics, 2012)

Exploring the spectrum of dynamical regimes and timescales in spontaneous cortical activity - Maurizio Mattia; Maria V. Sanchez-Vives (Cognitive Neurodynamics, 2012)

Human metapneumovirus strains circulating in Latin America - Josefina Garcia; Merly Sovero; Tadeusz Kochel; V. Alberto Laguna-Torres; Maria Ester Gamero; Jorge Gomez; Felix Sanchez; Ana E. Arango; Sergio Jaramillo; Eric S. Halsey (Archives of Virology, 2012)

Detection of human-induced environmental disturbances in a show cave - Angel Fernandez-Cortes; Soledad Cuezva; Sergio Sanchez-Moral; Juan Carlos Cañaveras; Estefania Porca; Valme Jurado; Pedro Maria Martin-Sanchez; Cesareo Saiz-Jimenez (Environmental Science and Pollution Research, 2011)

Methyl-β-Cyclodextrins Preferentially Remove Cholesterol from the Liquid Disordered Phase in Giant Unilamellar Vesicles - Susana A. Sanchez; German Gunther; Maria A. Tricerri; Enrico Gratton (The Journal of Membrane Biology, 2011)

Evolution of nematode-resistant Mi-1 gene homologs in three species of Solanum - Maria Virginia Sanchez-Puerta; Ricardo Williams Masuelli (Molecular Genetics and Genomics, 2011)

Tissue-specific expression of olive S-adenosyl methionine decarboxylase and spermidine synthase genes and polyamine metabolism during flower opening and early fruit development - Maria C. Gomez-Jimenez; Miguel A. Paredes; Mercedes Gallardo; Nieves Fernandez-Garcia; Enrique Olmos; Isabel M. Sanchez-Calle (Planta, 2010)

Methamphetamine and lentivirus interactions: Reciprocal enhancement of central nervous system disease - Salvador Huitron-Resendiz; Steven J Henriksen; Margaret C Barr; Maria P Testa; Elena Crawford; Loren H Parsons; Manuel Sanchez-Alavez; Tom R Phillips (Journal of NeuroVirology, 2010)

Nitrogen-Use Efficiency in Relation to Different Forms and Application Rates of Se in Lettuce Plants - Juan J. Ríos; Begoña Blasco; Luis M. Cervilla; Maria M. Rubio-Wilhelmi; Miguel A. Rosales; Eva Sanchez-Rodriguez; Luis Romero; Juan M. Ruiz (Journal of Plant Growth Regulation, 2010)

Derivation, characterization, differentiation, and registration of seven human embryonic stem cell lines (VAL-3, -4, -5, -6M, -7, -8, and -9) on human feeder - Cristobal Aguilar-Gallardo; Maria Poo; Eva Gomez; Amparo Galan; Eva Sanchez; Ana Marques-Mari; Veronica Ruiz; Jose Medrano; Marcia Riboldi; Diana Valbuena; Carlos Simon (In Vitro Cellular & Developmental Biology - Animal, 2010)

Ischemic preconditioning improves maximal performance in humans - Patricia C. E. de Groot; Dick H. J. Thijssen; Manuel Sanchez; Reinier Ellenkamp; Maria T. E. Hopman (European Journal of Applied Physiology, 2010)

Multiparametric comparison of mesenchymal stromal cells obtained from trabecular bone by using a novel isolation method with those obtained by iliac crest aspiration from the same subjects - Fermin M. Sanchez-Guijo; Juan F. Blanco; Graciela Cruz; Sandra Muntion; Maria Gomez; Soraya Carrancio; Olga Lopez-Villar; Maria-Victoria Barbado; Luis-Ignacio Sanchez-Abarca; Belén Blanco; Jesus G. Briñon; Maria-Consuelo del Cañizo (Cell and Tissue Research, 2009)

Coversand and Pleistocene palaeosols in the Landes region, southwestern France - Pascal Bertran; Giselle Allenet; Thierry Gé; Filipa Naughton; Philippe Poirier; Maria F. Sanchez Goñi (Journal of Quaternary Science, 2009)
New sections in the coversand of the Landes region, southwestern France, show at least two main depositional phases corresponding to the Upper Pleniglacial and the Lateglacial, which are separated by palaeosols. The lower palaeosol, a gleyic to histic cryosol overlying a net of sand wedges and dated to ca. 23 14 C ka BP, testifies to a short occurrence of permafrost. Impeded drainage due to the frozen subsoil is assumed to be the main factor involved in lowered aeolian transport and soil formation. Pollen analysis indicates a shrub tundra‐type environment. The overlying coversand unit is associated with small transverse ridges or sheet‐like deposits, and corresponds to the maximal extension of the sands, Upper Pleniglacial in age. An incipient podzol developed on the dunes under a boreal pine forest, and has been dated to 11.5–12 14 C ka BP, i.e. to the Allerød period. This has been buried by the second coversand unit during the Younger Dryas, typified by abundant denivation features and root imprints. Although preliminary, the chronology of sand deposition in the Landes region appears thus to be roughly similar to that found for the other European coversands, showing that all were the result of similar western European climatic changes, i.e. repeated episodes of increasing aridity related to the Upper Pleniglacial and the Younger Dryas episode. Copyright © 2008 John Wiley & Sons, Ltd.

Behavioral studies on tarsal gustation in honeybees: sucrose responsiveness and sucrose-mediated olfactory conditioning - Maria Gabriela de Brito Sanchez; Chun Chen; Jianjun Li; Fanglin Liu; Monique Gauthier; Martin Giurfa (Journal of Comparative Physiology A, 2008)

Anthocyanins: from plant to health - Sonia de Pascual-Teresa; Maria Teresa Sanchez-Ballesta (Phytochemistry Reviews, 2008)

Genotypic variability and persistence of Legionella pneumophila PFGE patterns in 34 cooling towers from two different areas - Inma Sanchez; Marian Garcia‐Nuñez; Sonia Ragull; Nieves Sopena; Maria Luisa Pedro‐Botet; Maria Esteve; Celestino Rey‐Joly; Miquel Sabria (Environmental Microbiology, 2008)

Genotypic variability and persistence of Legionella pneumophila PFGE patterns in 34 cooling towers from two different areas - Inma Sanchez; Marian Garcia‐Nuñez; Sonia Ragull; Nieves Sopena; Maria Luisa Pedro‐Botet; Maria Estere; Celestino Rey‐Joly; Miquel Sabria (Environmental Microbiology, 2008)
Summary Genotypic variability and clonal persistence are important concepts in molecular epidemiology as they facilitate the search for the source of sporadic cases or outbreaks of legionellosis. We studied the genotypic variability and persistence of Legionella pulsed‐field gel electrophoresis (PFGE) patterns over time (period > 6 months) in 34 positive cooling towers from two different areas. In area A, radius of 70 km, 52 indistinguishable PFGE patterns were differentiated among the 27 cooling towers. In 13 cooling towers we observed ≥ 2 PFGE patterns. Each cooling tower had its own indistinguishable Legionella PFGE pattern which was not shared with any other cooling tower. In area B, radius of 1 km, 10 indistinguishable PFGE patterns were obtained from the seven cooling towers. In four, we observed ≥ 2 PFGE patterns. Three of these 10 indistinguishable PFGE patterns were shared by more than one cooling tower. In 27 of 34 cooling towers the same PFGE pattern was recovered after 6 months to up to 5 years of follow‐up. The large genotypic diversity of Legionella observed in the cooling towers aids in the investigation of community outbreaks of Legionnaires' disease. However, shared patterns in small areas may confound the epidemiological investigation. The persistence of some PFGE patterns in cooling towers makes the recovery of the Legionella isolate causing the outbreak possible over time.

Inferring the skeleton cell cycle regulatory network of malaria parasite using comparative genomic and variational Bayesian approaches - Isabel M. Tienda-Luna; Yufang Yin; Maria C. Carrion; Yufei Huang; Hong Cai; Maribel Sanchez; Yufeng Wang (Genetica, 2007)

Water-Soluble Ions and Trace Metals in Airborne Particles Over Urban Areas of the State of São Paulo, Brazil: Influences of Local Sources and Long Range Transport - Pérola C. Vasconcellos; Rajasekhar Balasubramanian; Roy E. Bruns; Odon Sanchez-Ccoyllo; Maria F. Andrade; Marlene Flues (Water, Air, & Soil Pollution, 2007)

Swelling related to ettringite crystal formation in chromite ore processing residue - Deok Hyun Moon; Dimitris Dermatas; Mahmoud Wazne; Adriana M. Sanchez; Maria Chrysochoou; Dennis G. Grubb (Environmental Geochemistry and Health, 2007)

Effect of ectoparasitic Pimeliaphilus plumifer mites (Acari: Pterygosomatidae) on Meccus pallidipennis (Hemiptera: Reduviidae) and several other Chagas’ disease vectors under laboratory conditions - Abisai Martinez-Sanchez; Alejandro D. Camacho; Maria Teresa Quintero-Martinez; Ricardo Alejandre-Aguilar (Experimental and Applied Acarology, 2007)

Glycemic Load, Glycemic Index, and the Risk of Breast Cancer Among Mexican Women - Martin Lajous; Walter Willett; Eduardo Lazcano-Ponce; Luisa Maria Sanchez-Zamorano; Mauricio Hernandez-Avila; Isabelle Romieu (Cancer Causes & Control, 2005)

Play behavior and motor development in juvenile Belding?s ground squirrels ( Spermophilus beldingi ) - Scott Nunes; Eva-Maria Muecke; Zaira Sanchez; Rebekah R. Hoffmeier; Lesley T. Lancaster (Behavioral Ecology and Sociobiology, 2004)

Detection of QTL affecting fatty acid composition in the pig - Alex Clop; Cristina Ovilo; Miguel Perez-Enciso; Albert Cercos; Anna Tomas; Ana Fernandez; Agustina Coll; Josep M. Folch; Carmen Barragan; Isabel Diaz; Maria A. Oliver; Luis Varona; et al. (Mammalian Genome, 2003)

rRNA genes map to chromosomes 10, 11 and 12 in European whitefish (Coregonus lavaretus) and to chromosomes 1, 5, 9 and 10 in vendace (Coregonus albula) - Malgorzata Jankun; Paulino Martinez; Belen G. Pardo; Petr Rab; Maria Rabova; Laura Sanchez (Chromosome Research, 2000)

Changes in sleep after acute and repeated administration of nicotine in the rat - Rafael J. Salin-Pascual; Maria Luisa Moro-Lopez; Hector Gonzalez-Sanchez; Carlos Blanco-Centurion (Psychopharmacology, 1999)

The allotypic patchwork pattern of the rabbit IGKC1 allele b5wf : genic exchange or common ancestry? - W. van der Loo; Florence Mougel; Christianne Bouton; Maria S. Sanchez; Monnique Monnerot (Immunogenetics, 1999)

The role of muscle spindles in ankle movement perception in human subjects with diabetic neuropathy - R. W. M. van Deursen; Maria Matilde Sanchez; Jan S. Ulbrecht; P. R. Cavanagh (Experimental Brain Research, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)